Cellulose-derived polymer-based resin compositions and articles manufactured using the compositions
Patent Information
- Application Number
- JP2024207862
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2017-06-01
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-05
AI Technical Summary
【0007】 【0007】これらのバイオベースのプラスチック材料は、他のエンジニアリング熱可塑性材料よりも良好に成形物品に加工することができ、成形された物品は、他の材料から製造される物品よりも高い剛性を有し、他のバイオプラスチックから製造される物品よりも優れた靱性を有し、他のエンジニアリング熱可塑性材料から製造される物品よりも優れた応力亀裂抵抗を有することができる。
Smart Images

Figure 2025029020000001 
Figure 2025029020000002 
Figure 2025029020000003
Abstract
Description
[Technical field]
[0001]
[0001] The present invention is in the field of polymer-based resins derived from cellulose, particularly cellulose esters useful for relatively high temperature applications. Plastic articles made with these compositions, such as eyeglass frames, automobile parts, housings, and toys, are also provided. [Background technology]
[0002]
[0002] There is an increasing interest in materials made from bio-based raw materials such as wood, cotton, or corn. Wood is a more preferred raw material than corn because it does not have the potential to compete with the use of bio-based resins as a food source. Furthermore, conventional materials made from corn, such as polylactic acid (PLA), have limitations in terms of physical properties, which limits the range of applications in which they can be used.
[0003] It would be beneficial to provide a bio-based material with physical properties that can compete with engineering plastics such as polycarbonate, nylon, or ABS in a range of applications. Cellulose acetate compositions have been used for molding articles, but usually have a heat distortion temperature (HDT) below 90°C. Commercially available cellulose esters used in melt processing and molding of articles usually contain a significant amount of plasticizer to allow processing and provide toughness to the molded article. However, adding plasticizers has disadvantages because it reduces the HDT compared to the base cellulose ester, limiting the use of cellulose ester materials to applications that can accept a HDT below about 90°C. Also, cellulose ester molded articles can experience exudation of the plasticizer during use. Summary of the Invention [Problem to be solved by the invention]
[0004] It would be advantageous to provide cellulose-derived polymer-based resins that can be melt processed, and articles made from such compositions that do not suffer from these drawbacks. [Means for solving the problem]
[0005]
[0005] Surprisingly, it has been found that compositions of cellulose esters can be produced that have a significant bio-based content and an HDT of greater than 90°C or 95°C. In some embodiments of the present invention, this can be accomplished by reducing the amount of plasticizer in the composition, and in some embodiments, eliminating the use of plasticizers, while maintaining a good balance of physical properties and the ability to process the composition in conventional molding operations. Eliminating plasticizers can eliminate problems associated with exudation of plasticizers during use.
[0006] It has now been discovered that molded articles can be produced from bio-based plastic materials that have properties equivalent to or better than those of molded articles produced from petroleum-based engineering thermoplastic materials. More specifically, these molded articles are produced from bio-based plastic materials that have a heat distortion temperature (HDT) greater than 90° C. or greater than 95° C. This elevated HDT allows the molded articles to withstand high temperature environments (i.e., dishwashing, holding hot liquids, exposure to the sun, etc.), resist creep and warping during storage in high temperature warehouses or during use in applications under moderate loads or stresses, and resist loss of dimensional stability during use. This will greatly improve your ability to block attacks.
[0007]
[0007] These bio-based plastic materials can be processed into molded articles better than other engineering thermoplastics, and the molded articles can have higher stiffness than articles made from other materials, better toughness than articles made from other bioplastics, and better stress crack resistance than articles made from other engineering thermoplastics.
[0008] In one aspect, the invention provides a molded article comprising a cellulose-derived polymer-based resin, the polymer-based resin having an HDT of at least 90° C., or at least 95° C., a bio-based content of at least 20% by weight; and a flexural modulus of greater than 1900 MPa as measured in accordance with ASTM-D790 using 3.2 mm thick bars at 23° C. and 50% relative humidity for 48 hours; a notched Izod impact strength of greater than 80 J / m as measured in accordance with ASTM-D256 using 3.2 mm thick bars at 23° C. and 50% relative humidity for 48 hours; and a mold pressure of greater than 100% by weight, the polymer-based resin being molded in a spiral flow mold at a barrel temperature of 238° C., a melt temperature of 246° C., a molding pressure of 13.8 MPa, a mold thickness of 0.8 mm, and a mold width of 12.7 mm. a spiral flow length of at least 3.0 cm when molded at 90°C; a bending creep deflection of less than 12 mm when measured using a molded bar having dimensions of 5 inches long, 0.5 inches wide, and 0.125 inches thick, placed horizontally inside a drying oven at 90°C for 68 hours with a nominal stress of 500 psi on the center of the span on a fixture with a 4 inch span; a transmission of at least 70% when measured using a 3.2 mm plaque after injection molding at a barrel set point of 249°C and a 5 minute residence time according to ASTM-D1003; a ΔE value of less than 25 when measured using a 3.2 mm plaque after injection molding at a barrel temperature of 249°C and a 5 minute residence time; or an L of at least 85 when measured using a 3.2 mm plaque after injection molding at a barrel temperature of 249°C and a 5 minute residence time according to ASTM-E1348. *and color value. In some embodiments, the polymer-based resin has at least two, or at least three of the listed characteristics. In some embodiments, the polymer-based resin includes a plasticizer in an amount of 1-15 wt%, or 1-10 wt%, or 1-9 wt%, or no plasticizer. In some embodiments, the polymer-based resin includes less than 5 wt%, or less than 4 wt%, or less than 3 wt%, or less than 2 wt%, or less than 1 wt%, or no plasticizer is added.
[0009]
[0009] In some aspects of the present invention, the molded article may be selected from an injection molded article, an extrusion molded article, a rotational molded article, a compression molded article, a blow molded article, an injection blow molded article, an injection stretch blow molded article, an extrusion blow molded article, a sheet or film extrusion article, a profile extrusion article, a gas-assisted molded article, a structural foam molded article, or a thermoformed article.
[0010]
[0010] In some embodiments of the present invention, the molded article is selected from an opaque article, a transparent article, a see-through article, a thin-walled article, an industrial article (e.g., an article having a complex design), an article having advanced design specifications, an article having an intricate design, an article produced from a mold that is difficult to fill under normal molding operations or conditions, a worn article, an article that contacts the body, a container (including a container for materials intended to contact the body), a food contact article, a household article, a general consumer product, a packaging article, a medical article, or parts thereof.
[0011] In some embodiments, the transparent or see-through article is an electronic display, an electronic display lens or window, an electronic display cover, an ophthalmic device, an ophthalmic lens, an ophthalmic frame, sunglasses, a sunglass lens, an automotive interior component, a lighting fixture, an LED. The article may be selected from lights, lighting covers, headlight covers or enclosures, appliance parts, sporting goods, automotive parts, instrumentation parts, instrumentation covers, timing device parts, personal equipment, personal electronic devices, medical equipment, personal protective equipment, safety equipment, tools, protective gear, office supplies, kitchen utensils, kitchen items, cutlery, glassware, barware, artist supplies, decorative items, packaging, or parts thereof.
[0012]
[0012] In some embodiments, the thin-walled article can be selected from packaging articles (e.g., food containers and lids), articles for automobiles or other vehicles (e.g., both structural and non-structural parts of automobiles), mobile communication devices or portable electronic articles (e.g., cell phone housings), medical articles (e.g., syringes and connectors), articles for computing devices (e.g., computer housings), electronic devices, electronic device components, business equipment housings, electronic device housings, optical or electrical connectors, electronic device covers, electronic device screens, touch screens, covers for screens or touch screens, or parts thereof.
[0013]
[0013] In some embodiments, the industrial articles, articles with advanced design specifications, articles with intricate designs, and articles that are difficult to mold may be selected from transportation or automotive parts, electrical / electronic equipment parts, perfume or cosmetic containers, ophthalmic instruments, lighting instruments, timing instruments, medical instruments, or parts thereof.
[0014]
[0014] In some embodiments, the worn or body-contacting article may be selected from eyeglass frames, eyeglass lenses, sunglass frames, sunglass lenses, goggles, wearable electronic devices, headphones, earphones, watches, personal devices, personal electronic devices, medical devices, personal protective devices, safety equipment, jewelry, water sports equipment, or parts thereof.
[0015] In some embodiments, the household item or general consumer product may be selected from kitchenware, barware, outdoor furniture, indoor furniture, furniture parts, shelving, shelf dividers, slatwall, toys, luggage, electrical appliances, small appliances, storage containers, office supplies, bathroom equipment or fixtures, tools, consumer electronics, or parts thereof.
[0016] In some embodiments, the packaging article can be selected from a packaging system, product packaging, rigid medical packaging, a container, a thin-walled cup, a beaker, a bucket, a pail, a collapsible box, a crate, or components thereof.
[0017] In some embodiments, the medical article or device may be selected from a disposable, a syringe, tubing, a device, instrumentation, a handle, a medical package, a medical container, a housing, or a component thereof.
[0018] In another aspect, the invention is an injection molded article including a thin-walled body portion formed from a cellulose-derived polymer-based resin, the thin-walled body portion comprising: (i) Gate location; (ii) final filling position; (iii) a flow length to wall thickness ratio (wherein the flow length is measured from the gate location to the final fill location) of 100 or greater; and (iv) a wall thickness of about 2 mm or less; having; The polymer-based resin has an HDT of at least 90° C., or at least 95° C., a bio-derived content of at least 20% by weight, or at least 40% by weight, and a spiral flow length of at least 3.0 cm when the polymer-based resin is molded in a spiral flow mold under the following conditions: a barrel temperature of 238° C., a melt temperature of 246° C., a molding pressure of 13.8 MPa, a mold thickness of 0.8 mm, and a mold width of 12.7 mm. In some embodiments, the polymer base resin has a spiral flow length of at least 4.0 cm, or at least 5.0 cm.
[0019] In one embodiment of the injection molded article, the polymer base resin has a flexural modulus of greater than 1900 MPa as measured in accordance with ASTM-D790 using 3.2 mm thick bars at 23° C. and 50% relative humidity for 48 hours; a notched Izod impact strength of greater than 80 J / m as measured in accordance with ASTM-D256 ... and a flexural modulus of greater than 1900 MPa as measured in accordance with ASTM-D256 using 3.2 mm thick bars placed horizontally at 23° C. and 50% relative humidity for 68 hours at 90° C. on a 4 inch span fixture. a bending creep deflection of less than 12 mm as measured using molded bars having dimensions of 0.5 inches, 0.125 inches wide, and 0.5 inches thick; a transmission of at least 70 as measured using a 3.2 mm plaque after injection molding at a barrel set point of 249° C. and a 5 minute residence time according to ASTM-D1003; a ΔE value of less than 25 using a 3.2 mm plaque after injection molding at a barrel temperature of 249° C. and a 5 minute residence time; or an L of at least 85 as measured using a 3.2 mm plaque after injection molding at a barrel temperature of 249° C. and a 5 minute residence time according to ASTM-E1348. * and color value. In some embodiments, the polymer-based resin has at least two, or at least three of the listed properties. In some embodiments, the polymer-based resin contains less than 5% by weight, or less than 4% by weight, or less than 3% by weight, or less than 2% by weight, or less than 1% by weight of plasticizer, or no added plasticizer.
[0020] In some embodiments, the gate location includes a gate having a gate dimension, and a ratio of the gate dimension to the wall thickness is 1:1 or less, or 0.5:1 or less. In some embodiments, the gate dimension is 1.0 mm or less, or 0.5 mm or less. In some embodiments, the wall thickness is 1.5 mm or less, or 1.0 mm or less, or 0.5 mm or less.
[0021] In another aspect of the invention, the invention provides a housing comprising a cellulose-derived polymer-based resin, the polymer-based resin having an HDT of at least 90° C., or at least 95° C., a bio-derived content of at least 20% by weight, and a flexural modulus of greater than 1900 MPa as measured in accordance with ASTM-D790 using 3.2 mm thick bars at 23° C. and 50% relative humidity for 48 hours; a notched Izod impact strength of greater than 80 J / m as measured in accordance with ASTM-D256 using 3.2 mm thick bars at 23° C. and 50% relative humidity for 48 hours; and a flexural modulus of greater than 1900 MPa as measured in accordance with ASTM-D790 using 3.2 mm thick bars at 23° C. and 50% relative humidity for 48 hours; and a flexural modulus of greater than 1900 MPa as measured in accordance with ASTM-D256 using 3.2 mm thick bars at 23° C. and 50% relative humidity for 48 hours; a spiral flow length of at least 3.0 cm when molded using a 500 psi nominal stress on the center of the span on a 4 inch span fixture inside a drying oven for 68 hours at 90°C; a flexural creep deflection of less than 12 mm when measured using a molded bar having dimensions of 5 inches long, 0.5 inches wide, and 0.125 inches thick, placed horizontally at 90°C for 68 hours; a permeability of at least 70 when measured using a 3.2 mm plaque after injection molding at a barrel set point of 249°C and a 5 minute residence time according to ASTM-D1003; a ΔE value of less than 25 when measured using a 3.2 mm plaque after injection molding at a barrel temperature of 249°C and a 5 minute residence time according to ASTM-E1348; or an L of at least 85 when measured using a 3.2 mm plaque after injection molding at a barrel temperature of 249°C and a 5 minute residence time according to ASTM-E1348. * color value. In some embodiments, the polymer-based resin has at least two, or at least three of the listed characteristics. In some embodiments, the polymer-based resin contains less than 5% by weight, or less than 4% by weight, or less than 3% by weight, or less than 2% by weight, or less than 1% by weight of plasticizer, or no plasticizer is added. In one embodiment, the housing The housing is an electronic device housing.
[0022]
[0022] In some embodiments according to the various aspects of the invention disclosed herein, the polymer base resin comprises a cellulose ester. In some embodiments, the cellulose ester is selected from CA (cellulose acetate), CAP (cellulose acetate propionate), CAB (cellulose acetate butyrate), or CAIB (cellulose acetate isobutyrate) with a total degree of substitution ranging from 1.0 to 3.0. In one embodiment, the cellulose ester is CAP. In some embodiments of the invention, the CAP contains 0 to 5 wt%, 0 to 2 wt%, 0 to less than 2 wt%, 0 to 1 wt%, or no added plasticizer.
[0023] In some embodiments of the present invention, the polymer base resin comprises a cellulose ester; and optionally a plasticizer, where the plasticizer, if present, is present in an amount less than 20% by weight based on the total weight of the composition, the polymer base resin has a heat distortion temperature (HDT) greater than 90°C or greater than 95°C, as measured at 1.82 MPa using 1.3 cm x 12.7 cm x 0.32 cm bars subjected to 70°C and 50% relative humidity for 4 hours according to ASTM-D638, and has a weight average molecular weight (M) of 1.0 to 1.5 g / mol when the composition is injection molded at a barrel temperature of 260°C with a residence time of 5 minutes. w ) changes by less than 30%.
[0024] In some embodiments, the polymer-based resin comprises a cellulose ester and a dispersion of one or more impact modifiers in the cellulose ester in the form of small discrete particles in an amount sufficient to improve the mechanical and physical properties of the polymer-based resin, and the impact-modified cellulose ester resin is melt processable.
[0025]
[0025] In one aspect of the present invention, a polymer-based resin is provided that includes at least one cellulose ester, at least one impact modifier, and optionally at least one plasticizer. In one aspect, the cellulose ester is CAP and includes 0-1 wt. % of a plasticizer. In one aspect, the cellulose ester is CAP and includes no plasticizer.
[0026]
[0026] In another aspect of the present invention, a cellulose ester composition is provided that includes at least one cellulose ester, at least one impact modifier, and at least one plasticizer. In one aspect, the cellulose ester is CA and includes 1-15 wt% of the plasticizer. In some aspects, the cellulose ester is CA and includes 1-10 wt%, or 1-10 wt%, or 1-9 wt% of the plasticizer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] In one aspect, the invention provides a molded article comprising a cellulose-derived polymer-based resin, the polymer-based resin having an HDT of at least 90° C., or at least 95° C., a bio-derived content of at least 20% by weight; and a flexural modulus of greater than 1900 MPa as measured according to ASTM-D790 using 3.2 mm thick bars at 23° C. and 50% relative humidity for 48 hours; and a flexural modulus of greater than 80 J / m as measured according to ASTM-D256 using 3.2 mm thick bars at 23° C. and 50% relative humidity for 48 hours. High notched Izod impact strength; a spiral flow length of at least 3.0 cm when the polymer-based resin is molded in a spiral flow mold with a barrel temperature of 238°C, a melt temperature of 246°C, a molding pressure of 13.8 MPa, a mold thickness of 0.8 mm, and a mold width of 12.7 mm; a flexural creep deflection of less than 12 mm when measured using molded bars having dimensions of 5 inches long, 0.5 inches wide, and 0.125 inches thick, placed horizontally inside a drying oven at 90°C for 68 hours with a nominal stress of 500 psi on the center of the span on a fixture with a 4 inch span; A Permeability of at least 70 as measured using a 3.2 mm plaque after injection molding in accordance with STM-D1003 at a barrel set point of 249°C and a 5 minute residence time; a ΔE value of less than 25 using a 3.2 mm plaque after injection molding in accordance with ASTM-E1348 at a barrel set point of 249°C and a 5 minute residence time; or a L Permeability of at least 85 as measured using a 3.2 mm plaque after injection molding in accordance with ASTM-E1348 at a barrel set point of 249°C and a 5 minute residence time. * and color value. In some embodiments, the polymer-based resin has at least two, or at least three of the listed properties. In some embodiments, the polymer-based resin contains less than 5% by weight, or less than 4% by weight, or less than 3% by weight, or less than 2% by weight, or less than 1% by weight of plasticizer, or no added plasticizer.
[0028] In some embodiments, the invention provides a molded article comprising a cellulose-derived polymer-based resin, the polymer-based resin having an HDT of at least 90° C., or at least 95° C., a bio-based content of at least 20% by weight, a notched Izod impact strength of greater than 80 J / m as measured using 3.2 mm thick bars at 23° C. and 50% relative humidity for 48 hours according to ASTM-D256, and a flexural modulus of greater than 1900 MPa as measured using 3.2 mm thick bars at 23° C. and 50% relative humidity for 48 hours according to ASTM-D790; the polymer-based resin is molded using a spiral flow mold at a barrel temperature of 238° C., a melt temperature of 246° C., a molding pressure of 13.8 MPa, a mold thickness of 0.8 mm, and a mold width of 12.7 mm. a spiral flow length of at least 3.0 cm when molded at 90°C; a flexural creep deflection of less than 12 mm when measured using molded bars having dimensions of 5 inches long, 0.5 inches wide, and 0.125 inches thick, placed horizontally inside a drying oven at 90°C for 68 hours with a nominal stress of 500 psi on the center of the span on a fixture with a 4 inch span; a permeability of at least 70 when measured using a 3.2 mm plaque after injection molding at a barrel set point of 249°C and a 5 minute residence time according to ASTM-D1003; a ΔE value of less than 25 when measured using a 3.2 mm plaque after injection molding at a barrel temperature of 249°C and a 5 minute residence time; or an L of at least 85 when measured using a 3.2 mm plaque after injection molding at a barrel temperature of 249°C and a 5 minute residence time according to ASTM-E1348. * color value. In some embodiments, the polymer-based resin contains less than 5% by weight, or less than 4% by weight, or less than 3% by weight, or less than 2% by weight, or less than 1% by weight of a plasticizer, or no added plasticizer.
[0029] In some embodiments of the present invention, the polymer base resin has a heat distortion temperature (HDT) greater than 90°C, or greater than 95°C, measured according to ASTM D648 using 3.2 mm thick bars at 1.82 MPa at 70°C for 4 hours. In some embodiments, the polymer base resin has a heat distortion temperature (HDT) of at least 95°C, at least 100°C, at least 105°C, or at least 110°C, or at least 115°C. In some embodiments, the polymer-based resin is heated to 90°C to 140°C, 90°C to 130°C, 90°C to 120°C, 90°C to 110°C, 95°C to 140°C, 95°C to 130°C, 95°C to 120°C, 95°C to 110°C, 95°C to 105°C, 100°C to 140°C, 100°C to 130°C, 100°C to 120°C, 100°C to 110°C, 105°C to 140°C, 10 It has a heat distortion temperature (HDT) in the range of 5℃ to 130℃, 105℃ to 120℃, 105℃ to 115℃, 105℃ to 110℃, 110℃ to 140℃, 110℃ to 130℃, 110℃ to 125℃, 110℃ to 120℃, 110℃ to 115℃, 115℃ to 140℃, 115℃ to 130℃, 120℃ to 140℃, 120℃ to 130℃, or 120℃ to 125℃.
[0030]
[0030] Bio-based products are typically sourced through programs such as the USDA’s Bio First Program. These programs use ASTM method D6866-16 to measure the percentage of "new carbon" in the plastic materials from which the products are made. "New carbon" is carbon that comes from recently grown plants. This is compared to "old carbon" that comes from petroleum, natural gas, or coal. The "new carbon" content in the cellulose-based plastics used in this invention is typically 40%-60%, reflecting that the cellulose backbone in the cellulose material comes from trees or cotton.
[0031] In some embodiments of the present invention, the polymer-based resin has a bio-derived content of at least 20% by weight as measured according to ASTM method D6866-16. In some embodiments, the polymer-based resin has a bio-derived content of at least 25% by weight, or at least 30% by weight, or at least 35% by weight, or at least 40% by weight, or at least 45% by weight as measured according to ASTM method D6866-16. In some embodiments, the polymer-based resin has a bio-derived content in the range of about 20 to about 60 wt%, 20 to 50 wt%, 20 to 45 wt%, 25 to 60 wt%, 25 to 50 wt%, 25 to 45 wt%, 30 to 60 wt%, 30 to 50 wt%, 30 to 45 wt%, 35 to 60 wt%, 35 to 50 wt%, 35 to 45 wt%, 40 to 60 wt%, 40 to 50 wt%, or 40 to 45 wt%, as measured according to ASTM method D6866-16.
[0032] In some embodiments of the present invention, the polymer base resin has a flexural modulus of greater than 1800 MPa as measured according to ASTM-D790 using 3.2 mm thick bars at 23° C. and 50% relative humidity for 48 hours. In some embodiments, the polymer base resin has a flexural modulus of at least 1900 MPa, at least 2000 MPa, at least 2100 MPa, at least 2200 MPa, at least 2300 MPa, or at least 2400 MPa as measured according to ASTM-D790 using 3.2 mm thick bars at 23° C. and 50% relative humidity for 48 hours. In some embodiments, the polymer-based resin has a flexural modulus in the range of about 1800 to about 3500 MPa, about 1900 to about 3500 MPa, about 2000 to about 3500 MPa, about 2100 to about 3500 MPa, about 2200 to about 3500 MPa, about 2300 to about 3500 MPa, about 2400 to about 3500 MPa, or about 2500 to about 3500 MPa, as measured using 3.2 mm thick bars subjected to 48 hours at 23° C. and 50% relative humidity according to ASTM-D790. In some embodiments, the polymer base resin has a flexural modulus in the range of about 1900 to about 2500 MPa, about 1900 to about 2800 MPa, or about 1900 to about 3000 MPa, as measured according to ASTM-D790 using 3.2 mm thick bars subjected to 23° C. and 50% relative humidity for 48 hours.
[0033] In some embodiments of the present invention, the polymer base resin has a notched Izod impact strength of at least 40 J / m, or at least 60 J / m, as measured using 3.2 mm thick bars at 23° C. and 50% relative humidity for 48 hours, according to ASTM-D256. In some embodiments, the polymer base resin has a notched Izod impact strength of at least 80 J / m, or at least 90 J / m, or at least 100 J / m, or at least 110 J / m, or at least 120 J / m, or at least 130 J / m, or at least 140 J / m, or at least 150 J / m, as measured using 3.2 mm thick bars at 23° C. and 50% relative humidity for 48 hours, according to ASTM-D256. In some embodiments, the polymer-based resin has a viscosity of about 40 J / m to about 400 J / m, about 40 J / m to about 200 J / m, about 60 J / m to about 400 J / m, about 60 J / m to about 200 J / m, about 80 J / m to about 500 J / m, about 80 J / m to about 400 J / m, about 80 J / m to about 300 J / m, about 80 J / m to about 200 J / m, about 100 J / m to about 500 J / m, about 100 J / m to about 500 J / m, about 100 J / m to about 600 J / m, about 100 J / m to about 700 J / m, about 100 J / m to about 800 J / m, about 100 J / m to about 900 J / m, about 100 J / m to about 1500 J / m, about 100 J / m to about 200 J / m, about 100 J / m to about 300 J / m, about 100 J / m to about 400 J / m, about 100 J / m to about 500 J / m, about 100 J / m to about 600 J / m, about 100 J / m to about 1500 J / m, about 100 J / m to about 200 J / m, about 100 J / m to about 3 ...400 J / m, about 100 J / m to about 500 J / m, about 100 J / m to about 600 J / m, J / m to about 400 J / m, about 100 J / m to about 300 J / m, or about 100 J / m to about 200 J / m.
[0034] In some embodiments of the present invention, the polymer-based resin has a spiral flow length of at least 3.0 cm when the polymer-based resin is molded in a spiral flow mold with barrel temperature of 238° C., melt temperature of 246° C., molding pressure of 13.8 MPa, mold thickness of 0.8 mm, and mold width of 12.7 mm. In some embodiments, the polymer-based resin has a spiral flow length of at least 4 cm, or at least 5 cm when the polymer-based resin is molded in a spiral flow mold with barrel temperature of 238° C., melt temperature of 246° C., molding pressure of 13.8 MPa, mold thickness of 0.8 mm, and mold width of 12.7 mm. In some embodiments, the polymer-based resin has a spiral flow length in the range of about 3.0 cm to about 10.0 cm, about 4.0 cm to about 10.0 cm, about 5.0 cm to about 10.0 cm, about 4.0 cm to about 9.0 cm, about 4.0 cm to about 8.0 cm, about 4.0 cm to about 7.0 cm, or about 5.0 cm to about 7.0 cm when the polymer-based resin is molded using a spiral flow mold under conditions of a barrel temperature of 238° C., a melt temperature of 246° C., a molding pressure of 13.8 MPa, a mold thickness of 0.8 mm, and a mold width of 12.7 mm.
[0035] In some embodiments of the present invention, the polymer-based resin has a flexural creep deflection of less than 12 mm, or less than 11 mm, or less than 10 mm, when tested in accordance with ASTM-D2990 using injection molded bars having dimensions of 5 inches long, 0.5 inches wide, and 0.125 inches thick, placed horizontally on a fixture with a 4 inch span and a nominal stress of 500 psi on the center of the span, after 68 hours of exposure inside a 90° C. oven. In some embodiments, the polymer-based resin has a flexural creep deflection in the range of 2-12 mm, or 2-11 mm, or 2-10 mm, or 5-10 mm, when tested in accordance with ASTM-D2990 using injection molded bars having dimensions of 5 inches long, 0.5 inches wide, and 0.125 inches thick, placed horizontally on a fixture with a 4 inch span and a nominal stress of 500 psi on the center of the span, after 68 hours of exposure inside a 90° C. oven.
[0036] In some embodiments of the present invention, the polymer base resin has a Permeability measured using a 3.2 mm plaque after injection molding according to ASTM D1003 at a barrel set point of 249° C. and a 5 minute residence time of at least 70, or at least 75, or at least 80, or at least 85, or at least 90. In some embodiments, the polymer base resin has a Permeability measured using a 3.2 mm plaque after injection molding according to ASTM D1003 at a barrel set point of 249° C. and a 5 minute residence time in the range of 70-95, or 75-95, or 80-95, or 85-95, or 70-90, or 75-90, or 80-90, or 85-90.
[0037] In some embodiments of the present invention, the polymer base resin has a ΔE value of less than 25, or less than 20, or less than 15, or less than 14, or less than 13, or less than 12, or less than 11, or less than 10, or less than 9, or less than 8, or less than 7, or less than 6, or less than 5 using a 3.2 mm plaque after injection molding at a barrel temperature of 249° C. and a residence time of 5 minutes, where ΔE is determined by the following equation: ((L * -100) 2 +(a * -0) 2 +(b * -0) 2 ) 1 / 2 (In the formula, L * , a * , b * Color content is measured according to ASTM-E1348. In some embodiments, the polymer base resin has a ΔE value in the range of 2 to 25, or 2 to 20, or 2 to 15, or 2 to 14, or 2 to 13, or 2 to 12, or 2 to 11, or 2 to 10, or 2 to 9, or 2 to 8, or 2 to 7, or 2 to 6, or 2 to 5 using a 3.2 mm plaque after injection molding at a barrel temperature of 249° C. and a residence time of 5 minutes, where ΔE is determined by the following equation: ((L * -100) 2 +(a * -0)2 +(b * -0) 2 ) 1 / 2 (In the formula, L * , a * , b * Color The viscosity is determined by the following method: (minutes are measured according to ASTM-E1348).
[0038] In some embodiments of the present invention, the polymer base resin has an L of at least 85, or at least 86, or at least 87, or at least 88, or at least 89, or at least 90, or at least 91, or at least 92, or at least 93, or at least 94, or at least 95, as measured using 3.2 mm plaques after injection molding according to ASTM E1348 at a barrel temperature of 249° C. and a residence time of 5 minutes. * In some embodiments, the polymer base resin has a color value of 85-98, or 85-97, or 85-96, or 85-95, as measured using a 3.2 mm plaque after injection molding according to ASTM-E1348 at a barrel temperature of 249° C. and a residence time of 5 minutes. * It has a color value.
[0039] In some embodiments of the present invention, the polymer base resin has a b value of less than 15, or less than 12, or less than 10, or less than 9, or less than 8, or less than 7, or less than 6, or less than 5, or less than 4, as measured using 3.2 mm plaques after injection molding in accordance with ASTM E1348 at a barrel temperature of 249° C. and a residence time of 5 minutes. * In some embodiments, the polymer base resin has a b value ranging from 0 to 15, or 0 to 10, or 0 to 8, or 0 to 5, as measured using 3.2 mm plaques after injection molding according to ASTM-E1348 at a barrel temperature of 249° C. and a residence time of 5 minutes. * It has a value.
[0040] In some embodiments of the present invention, the polymer base resin has an injection molded absolute weight average molecular weight (M) of less than 30%, or less than 25%, or less than 20%, or less than 15%, or less than 10% when the composition is injection molded using a barrel temperature of 260° C. with a residence time of 5 minutes. w In some embodiments, the polymer base resin has a change in injection molding absolute weight average molecular weight (M) in the range of 0-30%, or 0-25%, or 0-20%, or 0-15%, or 0-10%, or 2-30%, or 2-25%, or 2-20%, or 2-15%, or 2-10% when the composition is injection molded using a barrel temperature of 260° C. with a residence time of 5 minutes. w ) changes.
[0041] In some embodiments of the present invention, the polymer base resin comprises a cellulose ester having an absolute weight average molecular weight in the range of about 40,000 Da to about 200,000 Da, as measured according to ASTM-D5296 using tetrahydrofuran as a solvent and a flow rate of 1 mL / min. In some embodiments, the cellulose ester has an absolute weight average molecular weight in the range of about 50,000 Da to about 200,000 Da, or 50,000 Da to about 170,000 Da, or 50,000 Da to about 120,000 Da, or 50,000 Da to about 90,000 Da, or 60,000 Da to about 200,000 Da, as measured according to ASTM-D5296 using tetrahydrofuran as a solvent and a flow rate of 1 mL / min. The absolute weight average molecular weight ranges from 0 Da, or 60,000 Da to about 170,000 Da, or 60,000 Da to about 120,000 Da, or 60,000 Da to about 90,000 Da, or 90,000 Da to about 170,000 Da, or 90,000 Da to about 120,000 Da, or 120,000 Da to about 170,000 Da, or 120,000 Da to about 200,000 Da.
[0042] In some aspects of the invention, the shaped article is not a continuous extruded film that is infinite (or continuous) in one direction and has a constant width and thickness in the other two directions, as is the case with rolled film. In some aspects, a film or sheet can be transformed into a shaped article by thermoforming into a three-dimensional object, such as a cup or bowl. In some aspects of the invention, the shaped article is not a film or is not a sheet. In some aspects of the invention, the shaped article is not a film or is not a sheet. In an embodiment, the molded article can be selected from an injection molded article, an extrusion molded article, a rotational molded article, a compression molded article, a blow molded article, an injection blow molded article, an injection stretch blow molded article, an extrusion blow molded article, a sheet or film extrusion article, a profile extrusion article, a gas-assisted molded article, a structural foam molded article, or a thermoformed article.
[0043]
[0043] Molded articles made from the polymer-based resins according to the present invention can be molded or extruded for use in the transportation, appliance, electronics, construction and building, biomedical, packaging, and consumer markets. In some embodiments of the present invention, the molded article is selected from transparent articles, see-through articles, thin-walled articles, industrial articles (e.g., articles with complex designs), articles with advanced design specifications, articles with intricate designs, articles made from molds that are difficult to fill under normal molding operations or conditions, worn articles, body contact articles, containers (including containers for materials intended for body contact), food contact articles, household articles, general consumer products, packaging articles, medical articles, or parts thereof.
[0044] In some embodiments, the polymer-based resin can be molded into shapes such as pellets, plates, and parisons, or can be molded into sheets, thin-walled containers, or thick-walled containers. Thin-walled containers can be processed into trays, blister packs, and the like; thick-walled containers can be processed into bottles, gardening containers, and the like. The polymer-based resin can also be processed into everyday items such as hoses, pipes, and the like, and industrial materials; cushioning materials in the form of foam, agricultural materials, and the like; industrial materials such as drainage materials, retaining walls, frameworks; and plant protection materials as ordinary moldings, and containers (for beverages, food, mechanical or electrical products, agricultural products, medicines, or seedling pots); household items such as eating utensils, knives, forks, spoons, trays, wallpaper, decorative paper, wrapping strings, pillows, and foam beads for cushions; medical tools; office supplies such as pen cylinders, files, tack sheets, and CDs, protective films for electronic devices, and the like; information media materials such as cards; outdoor supplies, sports supplies such as golf tees, and entertainment supplies, and the like.
[0045]
[0045] In some embodiments, the articles include, for example, enclosures, housings, panels, and components for outdoor vehicles and outdoor equipment; enclosures for electrical and telecommunications equipment; outdoor furniture; aircraft parts; boats and marine equipment (including trim, enclosures, and housings); outboard motor housings; depth gauge housings; personal watercraft; jet skis; swimming pools; spas; hot tubs; steps; step covers; architectural or construction applications such as glass, roofs, windows, floors, decorative window furnishings or treatments; treated glass covers for paintings, paints, posters, and similar display items; wallboard and doors; countertops; protective graphics; outdoor and indoor signage; enclosures, housings, panels, and components for automated teller machines (ATMs); computers; desktop computers; portable computers; laptop computers; housings for handheld computers; monitors; printers; keyboards; fax machines; copiers; telephones; telephone bezels; mobile phones; wireless. line transmitters; radio receivers; enclosures, housings, panels, and parts for lawn and garden tractors, mowers, and implements (lawn and garden tools); window and door trim; exercise equipment and toys; enclosures, housings, panels, and parts for snowmobiles; leisure vehicle panels and parts; amusement park equipment; shoe laces; articles made from plastic / wood combinations; golf course markers; drainage pit covers; lighting fixtures; lighting devices; network interface device housings; transformer housings; air conditioner housings; cladding or seating for public transportation; cladding or seating for trains, subways, or buses; instrument housings; antenna housings; cladding for satellite dishes; coated helmets and personal protective equipment; coated synthetic or natural fabrics; painted and coated articles; painted and dyed articles; painted fluorescent articles; painted foam articles; and similar electrical appliances.
[0046] In some embodiments, articles that may be manufactured in accordance with the present invention using the polymer-based resins include, for example, exterior and interior components of automobiles, aircraft, and watercraft, and may include, but are not limited to, instrument panels, overhead consoles, interior trim, center consoles, panels, quarter panels, rocker panels, trim, fenders, doors, decklids, trunk lids, hoods, bonnets, roofs, bumpers, dashboards, grilles, minor housings, pillar appliques, cladding, body side moldings, wheel covers, hubcaps, door handles, spoilers, window frames, headlamp bezels, headlamps, tail lamps, tail lamp housings, tail lamp bezels, license plate enclosures, roof racks, circuit breakers, electrical and electronics housings, and running boards, automotive bezels, automotive headlamp lenses (e.g., outer headlamp lenses or inner headlamp lenses), or headlamp assemblies including headlamp lenses, headlamp reflectors, bezels, and housings, or any combination thereof.
[0047] In some embodiments, articles using polymer-based resins comprising cellulose esters having the higher HDT and improved mechanical properties described herein can include automotive interior components (e.g., door handles, cup holders, dashboards, and glove boxes), electrical equipment components, food and beverage containers, food and beverage container lids, electrical and electronic equipment housings (e.g., computer monitor housings, laptop housings, cell phone housings), and the like.
[0048] Further examples of articles include disposable knives, forks, spoons, plates, cups, straws, as well as eyeglass frames, toothbrush handles, toys, automotive trim, tool handles, camera parts, electronic device parts, razor parts, ink pen barrels, disposable syringes, bottles, and the like. In one embodiment, the compositions of the present invention are useful as plastics, films, and sheets. In some embodiments, the compositions described herein are useful as plastics for making bottles, bottle caps, eyeglass frames, cutlery, disposable cutlery, cutlery handles, shelves, shelf dividers, electronic device housings, electronic device cases, computer monitors, printers, keyboards, pipes, automotive parts, automotive interior parts, automotive trim, signs, thermoformed letters, siding, toys, thermally conductive plastics, ophthalmic lenses, tools, tool handles, and household items. In other aspects, the compositions described herein are suitable for use as films, sheeting, molded articles, medical devices, packaging, bottles, bottle caps, eyeglass frames, cutlery, disposable cutlery, cutlery handles, shelves, shelf dividers, furniture parts, electronic device housings, electronic device cases, computer monitors, printers, keyboards, pipes, toothbrush handles, automotive parts, automotive interior parts, automotive trim, signs, outdoor signage, skylights, multilayer films, thermoformed letters, siding, toys, toy parts, thermally conductive plastics, ophthalmic lenses and frames, tools, tool handles, and household products, health care products, commercial food service products, boxes, films for graphic arts applications, and plastic films for plastic-glass laminates.
[0049]
[0049] The cellulose ester compositions described herein are useful for forming films, molded articles, and sheeting. The method of forming the cellulose ester compositions into films, molded articles, and sheeting can follow methods known in the art. Examples of possible molded articles include, without limitation, medical instruments, medical packaging, health care products, commercial food service products such as food pans, tumblers and storage boxes, bottles, food processors, blenders, and mixer bowls, household items, water bottles, These include crisper trays, washing machine fronts, vacuum cleaner parts, and toys. Other possible molded articles can include ophthalmic lenses and frames.
[0050]
[0050] The present invention further relates to articles of manufacture comprising one or more films and / or sheets comprising the cellulose ester compositions described herein. In some embodiments, the films and / or sheets of the present invention may be of any thickness apparent to one of ordinary skill in the art.
[0051]
[0051] The present invention further relates to one or more films and / or sheets described herein. The method of forming the cellulose ester composition into one or more films and / or sheets can include methods known in the art. Examples of the one or more films and / or sheets of the present invention include, but are not limited to, one or more extruded films and / or sheets, one or more calendered films and / or sheets, one or more compression molded films and / or sheets. Methods of producing the films and / or sheets include, but are not limited to, extrusion, compression molding, wet blocking, and dry blocking.
[0052] As discussed herein, in some embodiments of the present invention, the polymer base resin comprises at least one cellulose ester.
[0053] In some embodiments, the cellulose esters used in the present invention can be any known in the art. Cellulose esters that can be used for the present invention generally have the structure:
[0053] [ka]
[0054] (In the formula, R 1 , R 2 , and R 3 are independently selected from the group consisting of hydrogen or straight chain alkanoyl having 2 to 10 carbon atoms. Repeat units of 1.0 to 1.5.0. For cellulose esters, the substitution level is usually expressed as the degree of substitution (DS), which is the average number of non-OH substituents per anhydroglucose unit (AGU). Generally, conventional cellulose contains three hydroxyl groups in each AGU unit that can be substituted; therefore, the DS can have a value between 0 and 3. However, low molecular weight cellulose mixed esters may have a total degree of substitution slightly higher than 3 due to the contribution of end groups. Natural cellulose is a large polysaccharide with a degree of polymerization of 250 to 5,000 even after pulping and purification, so the assumption that the maximum DS is 3.0 is almost correct. However, as the degree of polymerization decreases, such as in low molecular weight cellulose mixed esters, the end groups of the polysaccharide backbone become relatively more significant, which results in a DS that can range above 3.0. Low molecular weight cellulose mixed esters are discussed in more detail below in this specification. Since DS is a statistical average, a value of 1 does not indicate that all AGUs have a single substituent. In some cases, there may be unsubstituted anhydroglucose units, some with two and some with three substituents, and usually this value is a non-integer. The total DS is the average of all the substituents per anhydroglucose unit. The degree of substitution per AGU may also refer to a specific substituent, such as, for example, hydroxyl, acetyl, butyryl, or propionyl.
[0055]
[0054] In some embodiments, the cellulose ester used may be a cellulose triester or a secondary cellulose ester. Examples of cellulose triesters include, but are not limited to, cellulose triacetate, cellulose tripropionate, or cellulose tributyrate. Examples of secondary cellulose esters include cellulose acetate, cellulose acetate propionate, and cellulose acetate butyrate.
[0056] In one embodiment of the present invention, the cellulose ester can be selected from cellulose acetate (CA), cellulose propionate (CP), cellulose butyrate (CB), cellulose acetate propionate (CAP), cellulose acetate butyrate (CAB), cellulose propionate butyrate (CPB), etc., or combinations thereof. Examples of such cellulose esters are described in U.S. Patents 1,698,049; 1,683,347; 1,880,808; 1,880,560; 1,984,147; 2,129,052; and 3,617,201 (all of which are incorporated herein by reference to the extent not inconsistent with the teachings herein).
[0057] In some embodiments of the present invention, the cellulose ester has at least two anhydroglucose rings and may have at least 50 to 5,000 anhydroglucose rings. The number of anhydroglucose units per molecule is defined as the degree of polymerization (DP) of the cellulose ester. In some embodiments, the cellulose ester may have an inherent viscosity (IV) of about 0.2 to about 3.0 deciliters / gram, or about 0.5 to about 1.8 deciliters / gram, or about 1 to about 1.5 deciliters / gram, measured at a temperature of 25° C. for a 0.25 gram sample in 100 mL of a 60 / 40 solution by weight of phenol / tetrachloroethane. Examples of cellulose esters include, but are not limited to, cellulose acetate, cellulose propionate, cellulose butyrate, cellulose acetate propionate (CAP), cellulose acetate butyrate (CAB), cellulose propionate butyrate, and the like. In some embodiments, the cellulose esters useful in the present invention may have a DS / AGU of about 2 to about 2.99, and the substituted esters may include acetyl, propionyl, and butyryl, or any combination thereof. In other embodiments of the present invention, the total DS / AGU ranges from about 2 to about 2.99, the acetyl DS / AGU ranges from about 0 to 2.2, and the remainder of the ester groups include propionyl, butyryl, or combinations thereof.
[0058]
[0057] The cellulose esters can be prepared by any method known in the art. Examples of methods for preparing cellulose esters can be found in Kirk-Othmer, Encyclopedia of Chemical Technology, 5th edition, vol.5, Wiley-Interscience, New York (2004), pp.394-444. The cellulose can be obtained in different grades and sources from cotton linters, softwood pulp, hardwood pulp, corn fiber, and other agricultural raw materials, and bacterial cellulose, among others.
[0059] One method for producing cellulose esters is the esterification of cellulose by mixing it with an appropriate organic acid, anhydride, and a catalyst. The cellulose is then converted to a cellulose triester. The ester is then hydrolyzed by adding a water-acid mixture to the cellulose triester, which can then be filtered to remove gel particles or fibers. Water is then added to the mixture to precipitate the cellulose ester. The cellulose ester is then washed with water to remove reaction by-products, and then dehydrated and dried. It is possible to do so.
[0060] The cellulose triester to be hydrolyzed may have three substituents independently selected from alkanoyl having 2 to 10 carbon atoms. Examples of cellulose triesters include cellulose triacetate, cellulose tripropionate, and cellulose tributyrate, or mixed triesters of cellulose such as cellulose acetate propionate and cellulose acetate butyrate. These cellulose esters can be prepared by a number of methods known to those skilled in the art. For example, cellulose esters can be prepared by heterogeneous acylation of cellulose in a mixture of carboxylic acid and anhydride in the presence of a catalyst such as H2SO4. Cellulose triesters can also be prepared by homogeneous acylation of cellulose dissolved in a suitable solvent such as LiCl / DMAc or LiCl / NMP.
[0061]
[0060] Those skilled in the art will understand that the trade term cellulose triester also includes cellulose esters that are not fully substituted by acyl groups. For example, cellulose triacetate commercially available from Eastman Chemical Company, Kingsport, TN, USA, usually has a DS of about 2.85 to about 2.99.
[0062] After esterification of cellulose to the triester, a portion of the acyl substituents can be removed by hydrolysis or alcoholysis to give secondary cellulose esters. As mentioned above, depending on the particular method used, the distribution of the acyl substituents can be random or non-random. Secondary cellulose esters can also be produced directly without hydrolysis by using a limited amount of acylating reagent. This process is particularly useful when the reaction is carried out in a solvent that dissolves cellulose. All of these methods produce the cellulose esters useful in the present invention.
[0063] In one embodiment, the secondary cellulose ester useful in the present invention has an absolute weight average molecular weight (Mw) of about 5,000 to about 400,000 as measured by gel permeation chromatography (GPC) according to ASTM-D6474. To calculate the absolute weight average molecular weight value (Mw) for CE, the following method is used: The solvent is THF stabilized with BHT preservative. The equipment for the THF / cellulose ester procedure consists of the following Agilent 1200 series components: degasser, isocratic pump, autosampler, column oven, UV / Vis detector, and refractive index detector. The test temperature is 30° C. and the flow rate is 1.0 mL / min. A sample solution of 25 mg of cellulose ester in 10 mL of THF with BHT preservative and 10 μL of toluene flow rate marker is prepared. The injection volume is 50 μL. The column set is Polymer Laboratories 5 μm-PLgel, Guard+Mixed C+Oligopore. Detection is by refractive index. Calibrants are monodisperse polystyrene standards from Polymer Laboratories, Mw=580-3,220,000. Universal calibration parameters are as follows: PS (K=0.0001280 and a=0.7120) and CE (K=0.00007572 and a=0.8424). The universal calibration parameters are determined by light scattering and viscometer to obtain accurate weight average molecular weight. In further embodiments, Mw is from about 15,000 to about 300,000. In further embodiments, Mw is in the range of about 10,000 to about 250,000; about 15000 to about 200000; about 20,000 to about 150,000; about 50,000 to about 150,000; or about 70,000 to about 120,000.
[0064]
[0063] Most commonly, commercial secondary cellulose esters are prepared by first acid-catalyzed heterogeneous acylation of cellulose to form a cellulose triester. After a homogeneous solution of the cellulose triester in the corresponding carboxylic acid is obtained, the cellulose triester is then subjected to hydrolysis until the desired degree of substitution is obtained. After isolation, random secondary cellulose esters are obtained. Cellulose esters are obtained, i.e., the relative degree of substitution (RDS) at each hydroxyl is approximately equal.
[0065] Some examples of cellulose esters which may be useful in the present invention can be prepared using techniques known in the art and are available from Eastman Chemical Company, Kingsport, Tenn., USA, such as Eastman® Cellulose Acetate. Eastman Cellulose Acetate Propionate CAP482-20 Cellulose Acetate Butyrate CAP141-20, Eastman® Cellulose Acetate Butyrate CAB381-20 , Cellulose Acetate Butyrate CAB171-15, and Eastman® Cellulose Acetate CA398-30.
[0066] In some embodiments, the cellulose esters used in the present invention may also contain chemical functional groups, which are described herein as either derivatized, modified, or functionalized cellulose esters. Functionalized cellulose esters can be prepared by reacting the free hydroxyl groups of the cellulose esters with a bifunctional reactant having one linking group for grafting to the cellulose ester and one functional group for providing a new chemical group to the cellulose ester. Examples of such bifunctional reactants include succinic anhydride, which is linked by an ester bond to provide an acid functionality; mercaptosilane, which is linked by an alkoxysilane bond to provide a mercapto functionality; and isocyanatoethyl methacrylate, which is linked by a urethane bond to provide a methacrylate functionality.
[0067] In one aspect of the invention, functionalized cellulose esters are prepared by reacting the free hydroxyl groups of a cellulose ester with a bifunctional reactant to produce a cellulose ester having at least one functional group selected from the group consisting of unsaturation (double bond), carboxylic acid, acetoacetate, acetoacetate imide, mercapto, melamine, and long alkyl chain.
[0068]
[0067] In one embodiment of the present invention, the cellulose ester can be selected from cellulose propionate (CP), cellulose butyrate (CB), cellulose acetate propionate (CAP), cellulose acetate butyrate (CAB), cellulose propionate butyrate (CPB), cellulose tripropionate (CTP), or cellulose tributyrate (CTB), but is not selected from cellulose acetate (CA).
[0069] In some embodiments, the polymer-based resin according to the present invention comprises a cellulose ester and, optionally, a plasticizer, where the plasticizer, if present, is present in an amount less than 20% by weight based on the total weight of the resin, and the resin has a heat distortion temperature in the range of about 90° C. to about 140° C., as measured at 1.82 MPa using 3.2 mm thick bars subjected to 70° C. for 4 hours according to ASTM-D648, and an injection molded absolute weight average molecular weight (M) when the resin is injection molded using a barrel temperature of 260° C. with a residence time of 5 minutes. w ) changes by less than 30%.
[0070] In some embodiments, when the polymer base resin is a cellulose ester composition, the weight average molecular weight (M) by injection molding is measured when the resin is injection molded using a barrel temperature of 260° C. and a residence time of 5 minutes. w ) changes by less than 25%, or less than 20%, or less than 15%, or less than 10%. In some embodiments, the injection molded weight average molecular weight (M) changes by less than 25%, or less than 20%, or less than 15%, or less than 10% when the resin is injection molded with a barrel temperature of 260° C. and a residence time of 5 minutes. w) may be in the range of 0 to 25%, or 0 to 20%, or 0 to 15%, or 0 to 10%.
[0071] In some embodiments, when the polymer-based resin comprises a cellulose ester composition, the molded article has low birefringence, substantially eliminating the undesirable rainbow effect that some plastics (e.g., engineering plastics) cause in polarized light. This low birefringence can improve user perception on electronic device screens and retail displays. In some embodiments, molded articles according to the present invention are in close proximity to articles molded using PMMA (e.g., articles made using Evonik CYRO Acrylite H12) and are similar to articles molded using polyester (e.g., Eastman Tritan TX1501HF) or polycarbonate (e.g., cellulose ester). Much better than articles molded using carbonites (e.g., Covestro Markrolon 2458). It has low birefringence.
[0072] In some embodiments, a salt stabilizer can be included in the cellulose ester composition to stabilize the cellulose ester composition during processing. The cationic component of the salt stabilizer is selected from aluminum, calcium, magnesium, copper, cobalt, manganese, barium, strontium, zinc, tin, cadmium, chromium, and iron cations; the anionic component of the salt stabilizer is selected from (C6-C 20 ) Alicyclic carboxylic acids, (C6-C 20 ) alkyl carboxylic acid, or (C6-C 20 ) Alkenyl carboxylic acid. (C6-C 20 ) Alicyclic carboxylic acids, (C6-C 20 ) alkyl carboxylic acid, or (C6-C 20Examples of alkenyl carboxylic acids include naphthenic acid, abietic acid, cyclohexane carboxylic acid, cyclohexane propionic acid, 3-methyl-cyclopentyl acetic acid, 4-methylcyclohexane carboxylic acid, 2,2,6-trimethylcyclohexane carboxylic acid, 2,3-dimethylcyclopentyl acetic acid, 2-methylcyclopentyl propionic acid, palmitic acid, stearic acid, oleic acid, lauric acid, etc. Examples of salt stabilizers include strontium naphthenate, copper naphthenate, magnesium naphthenate, copper abietic acid, magnesium abietic acid, etc.
[0073]
[0072] In one embodiment, the cellulose ester composition further comprises a salt stabilizer in the range of about 0.01 wt% to about 0.5 wt% based on the total weight of the composition. In one embodiment, the cellulose ester composition further comprises a salt stabilizer in the range of about 0.01 wt% to about 0.4 wt% based on the total weight of the composition. In one embodiment, the cellulose ester composition further comprises a salt stabilizer in the range of about 0.01 wt% to about 0.3 wt% based on the total weight of the composition. In one embodiment, the cellulose ester composition further comprises a salt stabilizer in the range of about 0.01 wt% to about 0.2 wt% based on the total weight of the composition. In one embodiment, the cellulose ester composition further comprises a salt stabilizer in the range of about 0.1 wt% to about 0.3 wt% based on the total weight of the composition. In one embodiment, the cellulose ester composition further comprises a salt stabilizer in the range of about 0.01 wt% to about 0.1 wt% based on the total weight of the composition.
[0074] In some embodiments of the present invention, the polymer-based resin may contain antioxidants and acid stabilizers, for example when the polymer-based resin is a cellulose ester composition. Antioxidants are chemicals used to prevent decomposition processes during processing of materials. Antioxidants are divided into several classes, such as primary antioxidants and secondary antioxidants.
[0075] A "primary antioxidant" is an antioxidant that acts by reacting with peroxide groups via hydrogen transfer to quench the radical. Primary antioxidants generally contain reactive hydroxy or amino groups, such as in hindered phenols and secondary aromatic amines. Examples of primary antioxidants include Irganox® 1010, 1076, 1726, 245, 1098, 259, and 1425; Ethanox® 310, 376, 314, and 330; Evernox® 1010, 1076, 1726, 245, 1098, 259, and 1425; Ethanox® 310, 376, 314, and 330; Anox® 10, 76, 1335, 1330, 3114, MD1024, 1098, 1726, 120, 2246, and 565; Anox® 20, 29, 330, 70, IC-14, and 1315; Lowinox® 520, 1790, 221B46, 22 M46, 44B25, AH25, GP45, CA22, CPL, HD98, TBM-6, and WSP; Naugard® 431 , PS48, SP, and 445; Songnox® 1010, 1024, 1035, 1076CP, 1135LQ, 1290PW, 1330FF, 1330PW, 2590PW, and 3114FF; and ADK Stab AO-20, AO-30, AO-40, AO-50 , AO-60, AO-80, and AO-330;
[0076] In one embodiment, the composition further comprises a primary antioxidant in the range of 0 to about 1.0 wt %, based on the total weight of the composition. In some embodiments, the composition further comprises a primary antioxidant in the range of about 0.1 to about 1.0 wt %, or about 0.2 to about 1.0 wt %, or about 0.3 to about 1.0 wt %, or about 0.4 to about 1.0 wt %, or about 0.5 to about 1.0 wt %, or about 0.6 to about 1.0 wt %, or about 0.7 to about 1.0 wt %, or about 0.8 to about 1.0 wt %, based on the total weight of the composition. In some embodiments, the composition comprises a primary antioxidant in the range of about 0.1 to about 0.8 wt %, or about 0.1 to about 0.6 wt %, or about 0.1 to about 0.4 wt %, based on the total weight of the composition.
[0077] "Secondary antioxidants" are often called hydroperoxide decomposers. They act by reacting with hydroperoxides to break them down into non-radical, non-reactive, thermally stable products. They are often used in combination with primary antioxidants. Examples of secondary antioxidants include the organophosphorus class of compounds (e.g., phosphites, phosphonites) and the organosulfur class of compounds. The phosphorus and sulfur atoms of these compounds react with peroxides to convert them to alcohols. Examples of secondary antioxidants include Ultranox® 626; Ethanox® 368; , 326, and 327; Doverphos® LPG11, LPG12, DP S-680, 4, 10, S480, and S-9228; Evernox® 168 and 626; Irgafos® 126 and 168; Weston® DPDP, DPP, EHDP, PDDP, TDP, and TPP; Mark® CH302, CH55, TNPP, CH66, CH300, CH301, CH302, CH304, and CH305; ADK Stab 2112, HP-10, PEP-8, PEP-36, 1178, 135A, 1500, 3010, C, and TPP; Weston 439, DHOP, DPDP, DPP, DPTDP, EHDP, PDDP, PNPG, PTP, PTP, TDP, TLP, TPP, 398, 399, 430, 705, 705T, TLTTP, and TNPP; Alkanox® 240, 626, 626A, 627AV, 618F, and 619F; and Songnox® ) 1680FF, 1680PW, and 6280FF;
[0078] In some embodiments, the composition further comprises a secondary antioxidant in the range of about 0.1 to about 0.8 wt.%, or about 0.2 to about 0.8 wt.%, or about 0.3 to about 0.8 wt.%, or about 0.4 to about 0.8 wt.%, or about 0.5 to about 0.8 wt.%, or about 0.6 to about 0.8 wt.%, based on the total weight of the composition. In some embodiments, the composition further comprises a secondary antioxidant in the range of about 0.1 to about 0.7 wt.%, or about 0.1 to about 0.6 wt.%, or about 0.1 to about 0.5 wt.%, or about 0.1 to about 0.4 wt.%, or about 0.1 to about 0.3 wt.%, based on the total weight of the composition. In some embodiments, the composition further comprises a secondary antioxidant in the range of about 0.3 to about 0.7 wt.%, or about 0.3 to about 0.6 wt.%, based on the total weight of the composition.
[0079] "Acid scavengers" are additives that neutralize acids formed during processing of a polymer. Examples of acid scavengers include Hycite 713; Kisuma DHT-4A, DHT-4V, DHT-4A-2, DHT-4C, ZHT-4V, and KW2200; Brueggemann Chemical zinc carbonate RAC; Sipax (registered trademark) Baerlocher GL 34, RSN, GP, and LA Veg; Licomont CAV 102; FACl calcium stearate DW, PLC, SP, and WLC; Hangzhou Hitech Fine Chemical: CAST and ZnST; Songstab® SC-110, SC-120, SC-130, SM-310, and SZ-210; Sun Ace SAK-CS, SAK-DSC, SAK-DMS, SAK-DZS, and SAK-KS; US Zinc zinc oxide 201, 205 HAS, 205H, 210, and 210E; Drapex® 4.4, 6.8, 39, 391, 392, and and 392S; Vikoflex® 4050, 5075, 7170, 7190, 7040, 9010, 9040, and 9080; Joncryl® ADR 4468, and ADR 4400; Adeka CIZER D-32; Epon® 100 1F, 1002F, and 1007F; Araldite® ECN 1299, 1273, 1280, 1299, and 9511 ;Dynamar RC 5251Q; and Nexamite PBO.
[0080]
[0079] In some embodiments, the composition further comprises an acid scavenger in the range of about 0.2 to about 2.0 wt%, or about 0.4 to about 2.0 wt%, or about 0.6 to about 2.0 wt%, or about 0.8 to about 2.0 wt%, or about 1.0 to about 2.0 wt%, or about 1.2 to about 2.0 wt%, or about 1.4 to about 2.0 wt%, or about 1.6 to about 2.0 wt%, or about 1.8 to about 2.0 wt%, based on the total weight of the composition. In some embodiments, the composition further comprises an acid scavenger in the range of about 0.2 to about 1.8 wt%, or about 0.2 to about 1.6 wt%, or about 0.2 to about 1.4 wt%, or about 0.2 to about 1.2 wt%, or about 0.2 to about 1.0 wt%, or about 0.2 to about 0.8 wt%, or about 0.2 to about 0.6 wt%, or about 0.2 to about 0.4 wt%, based on the total weight of the composition. In some embodiments, the composition further comprises an acid scavenger in the range of about 0.4 to about 1.8 wt%, or about 0.6 to about 1.6 wt%, or about 0.8 to about 1.4 wt%, or about 0.8 to about 1.2 wt%, based on the total weight of the composition.
[0081]
[0080] In one embodiment, the composition further comprises a secondary antioxidant in the range of about 0.1 to about 0.8 weight percent, based on the total weight of the composition; and an acid scavenger in the range of about 0.2 to about 2.0 weight percent, based on the total weight of the composition.
[0082]
[0081] In one embodiment, the composition further comprises a primary antioxidant in the range of about 0 to about 1.0 wt %, based on the total weight of the composition; a secondary antioxidant in the range of about 0.1 to about 0.8 wt %, based on the total weight of the composition; and an acid scavenger in the range of about 0.2 to about 2.0 wt %, based on the total weight of the composition.
[0083]
[0082] In one embodiment, the composition further comprises a secondary antioxidant in the range of about 0.1 to about 0.8 weight percent, based on the total weight of the composition; an acid scavenger in the range of about 0.2 to about 2.0 weight percent, based on the total weight of the composition; and an impact modifier in the range of 0 to about 15 weight percent, based on the total weight of the composition.
[0084]
[0083] In one embodiment, the composition further comprises a primary antioxidant in the range of about 0 to about 1.0 wt %, based on the total weight of the composition; a secondary antioxidant in the range of about 0.1 to about 0.8 wt %, based on the total weight of the composition; an acid scavenger in the range of about 0.2 to about 2.0 wt %, based on the total weight of the composition; and an impact modifier in the range of 0 to about 15 wt %, based on the total weight of the composition.
[0085] In some embodiments of the present invention, the impact modifier may be any material known to increase the impact strength of cellulose ester compositions. For purposes of the present invention, an impact modifier is defined as any material of which at least a portion of the composition is an elastomer having a glass transition temperature (Tg) below room temperature. Tg can be measured, for example, according to ASTM-D3418 using a TA2100 thermal analyzer and a scan rate of 20°C / min. Several classes of impact modifiers fit this description. In one embodiment, the composition further comprises an impact modifier in the range of 0 to about 15 weight percent based on the total weight of the composition.
[0086] In one embodiment, the impact modifier can be selected from the class of materials known as modified polyolefins. In this class, olefins are copolymerized with additional monomers that limit the crystallization of the polymer, increasing the amount of chains with a Tg below room temperature and reducing the modulus below 500 MPa. Examples of modified olefins include EMA (examples include Elvaloy 4051, Lotader 3410, and Lotader 8900), ... BA, EVA (examples include Levamelt 500, Levamelt 600, Levamelt 700, Levamelt 800, Elvax 40W, Evatane 28-40, Evatane 40-55, Evatane 18-150, Bynel E418, and Bynel 3101), EEA, EPDM (examples include Royaltuf 498), E Examples include PR.
[0087] In one class of these embodiments, the impact modifiers are block copolymers in which at least one segment of the chain has a Tg below room temperature (called the soft segment) and at least one segment of the chain has a Tg or Tm above room temperature (called the hard segment). These block copolymers are also commonly referred to as thermoplastic elastomers (TPEs). Examples of block copolymers in this class include SBS, SEBS, and SIS (e.g., Kraton G1657MS, Kraton FG1901G, and Kraton Styrenic materials such as styrene-based materials (examples include Elastolan 1170Z, Estane 2355, Estane ALR-CL87A, and Estane ALR-72A); thermoplastic urethanes (TPUs) (examples include Elastolan 1170Z, Estane 2355, Estane ALR-CL87A, and Estane ALR-72A); polyester-ether copolymers (examples include Ecdel 9966 and Hytrel 3078 ), or polyamide-ether copolymers (examples include Pebax 5533).
[0088] In one embodiment, the impact modifier can be selected from the class of emulsion forming materials known as core-shell impact modifiers. In one embodiment, the impact modifier is an MBS core-shell impact modifier, such as methacrylate-butadiene-styrene, having a core formed from a butadiene-styrene copolymer and a shell formed from a methyl methacrylate-styrene copolymer. In another embodiment, the impact modifier is an acrylic core-shell impact modifier, having a core formed from an acrylic polymer and a shell formed from a polymethyl methacrylate, such as methyl methacrylate / butyl acrylate.
[0089] In one embodiment of the present invention, the core-shell impact modifier comprises: (A) from about 70 to about 85 parts of a core comprising from about 15 to about 35 weight percent of units derived from at least one vinyl aromatic monomer and from about 65 to about 85 weight percent of units derived from at least one diolefin monomer; (B) an internal grafting stage comprising from about 8 to about 14 parts of at least one vinyl aromatic monomer or at least one C1-C4 alkyl methacrylate monomer; (C) from about 0.1 to about 5 parts of an intermediate sealer stage comprising at least one monomer selected from a C1 to C8 alkyl acrylate or a polyunsaturated crosslinker; and (D) an outer shell comprising from about 10 to about 16 parts of at least one C1-C4 alkyl (meth)acrylate monomer or at least one vinyl aromatic monomer; The MBS impact modifier may comprise
[0090] In some embodiments, the MBS impact modifier may comprise a graft polymer composition comprising 10 to 70 weight percent of a polymer or copolymer of butadiene and a graft of a first graft of methyl (meth)acrylate and a crosslinker, a second graft of styrene, and a third graft of methyl (meth)acrylate and optionally a crosslinker.
[0091] Suitable monomers for polymerizing with the conjugated diolefin, preferably butadiene, include alkenyl aromatic compounds, preferably vinyl aromatic compounds, such as styrene, divinylbenzene, α-methylstyrene, vinyltoluene, hydrogenated styrene; lower (CZ-Cu) alkyl acrylates, such as ethyl acrylate, n-propyl acrylate, n-butyl acrylate, Z-methylbutyl acrylate, 3-methylbutyl acrylate, amyl acrylate, n-hexyl acrylate, Z-ethylhexyl acrylate; lower (C2-C3) alkyl acrylates, such as ethyl acrylate, n-propyl acrylate, n-butyl acrylate, Z-methylbutyl acrylate, 3-methylbutyl acrylate, amyl acrylate, n-hexyl acrylate, Z-ethylhexyl acrylate; 12 ) Alkyl (meth)acrylate; Acrylonitrile; Olefin etc. or a combination of any of the above.
[0092]
[0091] Suitable crosslinking agents include divinylbenzene; di(meth)acrylates; diacrylates, such as mono-, di-, or diacrylates of polyethylene glycols; their (meth)acrylates; divinyl sulfide; divinyl ethers; vinyl acrylate; vinyl (meth)acrylate; trivinylbenzene; trimethylolpropane; tri(meth)acrylate; triallyl cyanurate and triallyl isocyanurate.
[0093] In one embodiment, the MBS core-shell impact modifier may comprise a copolymer of butadiene and styrene, or a terpolymer of butadiene, styrene, and divinylbenzene. The relative amounts of the monomers making up the copolymer substrate may vary, but based on 100 parts by weight of the total of butadiene, styrene, and divinylbenzene, the butadiene component will usually comprise from about 30 to 100 parts by weight, the styrene component may comprise from 0 to about 70 parts by weight, and the divinylbenzene component may comprise from 0 to about 5 parts by weight. In one embodiment, the copolymer substrate may comprise from about 50 to about 90 parts by weight of butadiene, from about 10 to about 50 parts by weight of styrene, and from 0 to about 5 parts by weight of divinylbenzene, on the same basis, or from about 65 to about 85 parts by weight of butadiene, from about 15 to about 35 parts by weight of styrene, and from about 0.5 to about 2.0 parts by weight of divinylbenzene, on the same basis.
[0094]
[0093] Examples of methacrylate-butadiene-styrene core-shell polymers include, but are not limited to, those described in patents US-4,446,585, US-5,534,594, and US-6,331,580. MBS core-shell impact modifiers are available from Kaneka as Kane Ace B564, from Arkema as Clearstrength, from Dow as Paraloid, and from Evonik as Visiomer.
[0095] In one class of this embodiment, the impact modifier is an ABS core-shell impact modifier. Examples of ABS core-shell impact modifiers include acrylonitrile-butadiene-styrene ABS core-shell impact modifiers having a core formed from a butadiene-styrene copolymer and a shell formed from an acrylonitrile-styrene copolymer.
[0096]
[0095] In one embodiment of the present invention, the core-shell impact modifier is an acrylic impact modifier comprising about 25-95% by weight of a first elastomeric phase polymerized from a monomer system comprising about 75-99.8% by weight of a (C1-C6) alkyl acrylate, 0.1-5% by weight of a crosslinking monomer, and 0.1-5% by weight of a graft linking monomer, and about 75-5% by weight of a final rigid thermoplastic phase containing no epoxy groups polymerized in the presence of such elastomeric phase.
[0097]
[0096] Examples of useful acrylates are methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, etc. In some embodiments, the acrylates are n-butyl acrylate and ethyl acrylate.
[0098] Examples of acrylic core-shell polymers include, but are not limited to, those described in patents US-3,448,173, US-3,655,825, and US-3,853,968. Examples of suitable acrylic impact modifiers include Kane Ace ECO100 from Kaneka, Durastrength from Arkema, Elvaloy and Elvaloy HP from DuPont, and Epoxy 100 from Dow. It is a Paraloid.
[0099] In one embodiment, the impact modifier is a carboxylic acid having a relatively neutral pH (e.g., between 6 and 8, Preferably, the composition has a pH between 6.5 and 7.5, which is believed to help prevent the cellulose esters from decomposing during melt processing of the composition.
[0100] In another embodiment, the refractive index (RI) of the impact modifier is close enough to that of the cellulose ester to provide a composition with high transmittance and low haze. In one embodiment, the acrylic impact modifier has an RI close to that of the cellulose ester, about 1.46 to 1.50, providing a transparent composition. In some embodiments, the impact modifier component and the cellulose ester component have a refractive index difference of RI(second component)-RI(first component) (e.g., RI of CE-RI of impact modifier) of about 0.006 to about -0.0006, and the immiscible blend has a transmittance of at least 75% and a haze of 10% or less, more preferably 5% or less.
[0101] In some embodiments, the composition further comprising an impact modifier has a viscosity of at least 7 5%, or at least 80%, or at least 85%, or at least 90%, or at least 95%. In one class of this embodiment, the composition further comprising an impact modifier has a % haze of less than 10%. In some embodiments, the composition further comprising an impact modifier has a % haze of less than 8%, or less than 6%, or less than 5%.
[0102] In one embodiment, the impact modifier is a non-reactive impact modifier or a reactive impact modifier. The impact modifier may be either a cellulose ester, a cellulose ester copolymer, a cellulose ester copolymer copolymer, or a combination of both. It is believed that some impact modifiers can also improve the mechanical and physical properties of the cellulose ester composition.
[0103] In one embodiment, when a non-reactive impact modifier is used, the impact modifier The agent comprises a first polymer chain segment that is more chemically or physically compatible with cellulose ester than other polymer chain segments. In one embodiment, the first segment comprises a polar functional group that confers compatibility with cellulose ester, such as, but not limited to, polar functional groups such as ether, ester, amide, alcohol, amine, ketone, and acetal. Compatibility is defined by the preferential interaction of the first polymer chain segment with the cellulose ester polymer over the second segment, which may refer to molecular-scale or micro-scale interactions. In one embodiment, the first segment is polyethylene vinyl acetate; polyoxyethylene, or polyvinyl alcohol.
[0104] In some embodiments, the second segment is either saturated or unsaturated. The second segment may be a hydrocarbon group or may contain both saturated and unsaturated hydrocarbon groups. The second segment may be an oligomer or a polymer. In one aspect of the present invention, the second segment of the non-reactive impact modifier is selected from the group consisting of polyolefins, polydienes, aromatic polymers, and copolymers. An example of an aromatic polymer second segment is polystyrene. An example of a copolymer second segment is a styrene / butadiene copolymer.
[0105]
[0104] Examples of non-reactive impact modifiers include ethoxylated alcohols, ethoxylated Examples of ethoxylated alcohols include, but are not limited to, ethoxylated alkylphenols, ethoxylated fatty acids, polyethylene vinyl acetate, block polymers of propylene oxide and ethylene oxide, ethylene / propylene terpolymers, functionalized polyolefins, polyglycerol esters, polysaccharide esters, and sorbitan esters. 11 ~C 15 Secondary alcohol ethoxylates, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, and C1 ethoxylated with ethylene oxide 2~C14 It is a natural linear alcohol. 11 ~C 15 A secondary alcohol ethoxylate is available from Dow Chemical Company as Dow Tergitol® 15S. Polyoxyethylene cetyl ether and polyoxyethylene stearyl ether are available from ICI Surfactants in their Brij® series of products. C ethoxylated with dimethyl ether 12 ~C 14 Natural linear alcohols are available from Hoechst Celanese in their Genapol® series of products. Examples of alkylphenols include octylphenoxypoly(ethyleneoxy)ethanol and nonylphenoxypoly(ethyleneoxy)ethanol. Octylphenoxypoly(ethyleneoxy)ethanol is available from Rhodia in the Igepal® CA series of products, and nonylphenoxypoly(ethyleneoxy)ethanol is available from Rhodia in the Igepal® CO series of products or from Dow Chemical Company as Tergitol® NP. Ethoxylated fatty acids include polyethylene glycols available from Henkel in the Nopalcol® series of products. Block polymers of propylene oxide and ethylene oxide are available from BASF in the Pluronic® series of products. Polyglycerol esters are available from Stepan under the Drewpol® brand. ) series of products from Henkel. Polysaccharide esters are available in the Glucopon® series of products, which are alkyl polyglucosides. Sorbitan esters are available in the Tween® series of products from ICI.
[0106] In another embodiment of the present invention, the non-reactive impact modifier is a cellulose ester. The cellulose ester composition is prepared in situ by reacting the cellulose ester with a compound compatible with the cellulose ester. These compounds may be, for example, telechelic oligomers, which are defined as prepolymers capable of initiating further polymerization or other reactions by virtue of their reactive end groups. In one aspect of the invention, these in situ impact modifiers may have a higher molecular weight (weight average molecular weight Mw) of about 10,000 to about 1,000,000.
[0107] In another embodiment of the present invention, the impact modifier may be reactive. The impact modifier may include a polymer or oligomer that is compatible with one component of the composition and a functional group that can react with the other component of the composition. In some embodiments, there are two types of reactive impact modifiers that can be used. The first reactive impact modifier has a hydrocarbon chain that is compatible with the cellulose ester and also has a functional group that can react with the cellulose ester. Such functional groups include, but are not limited to, carboxylic acid, anhydride, acid chloride, epoxide, and isocyanate. Specific examples of this type of reactive impact modifier include, but are not limited to, long chain fatty acids such as stearic acid (octadecanoic acid); long chain fatty acid chlorides such as stearoyl chloride (octadecanoyl chloride); long chain fatty acid anhydrides such as stearic anhydride (octadecanoic anhydride); epoxidized fatty esters; styrene maleic anhydride copolymers; maleic anhydride grafted polypropylene; copolymers of maleic anhydride with olefins and / or acrylic esters, such as terpolymers of ethylene, acrylic esters, and maleic anhydride; and copolymers of glycidyl methacrylate with olefins and / or acrylic esters, such as terpolymers of ethylene, acrylic esters, and glycidyl methacrylate.
[0108] The reactive impact modifier is SMA® 3000 from Sartomer / Cray Valley. Styrene-maleic anhydride copolymers, Eastman G-3015® maleic anhydride grafted polypropylene from Eastman Chemical Company, Epolene® E-43 maleic anhydride grafted polypropylene from Westlake Chemical, ethylene from Arkema, Lotader® MAH 8200 Random Mix of olefins, acrylic esters, and maleic anhydride Lotader® GMA AX8900 random terpolymer of ethylene, acrylic ester, and glycidyl methacrylate; and Lotarder® GMA AX8840 random terpolymer of glycidyl methacrylate.
[0109]
[0108] Modified polyolefin impact modifiers are available as Lotader, Fusabond, Elvloy PTW, Lotryl, Elvaloy AC, InterLoy. The second type of reactive impact modifier is a polar ester compatible with cellulose esters. The reactive impact modifier also has a functional group that has a chain and can react with cellulose ester. Examples of these types of reactive impact modifiers include cellulose esters or polyethylene glycols with olefinic or thiol functional groups. Examples of reactive polyethylene glycol impact modifiers with olefinic functional groups include, but are not limited to, polyethylene glycol allyl ether and polyethylene glycol acrylate. Examples of reactive polyethylene glycol impact modifiers with thiol functional groups include polyethylene glycol thiols. Examples of reactive cellulose ester impact modifiers include mercaptoacetate cellulose esters.
[0110] In some embodiments of the present invention, impact resistance in the cellulose ester composition The amount of the impact modifier may range from about 1% to about 30% by weight, or from about 1% to about 15% by weight, or from about 5% to about 10% by weight, or from about 10% to about 30% by weight, or from about 15% to about 30% by weight, based on the weight of the cellulose ester composition.
[0111] In another embodiment of the present invention, the cellulose ester composition comprises at least one The composition further comprises, as a blend (with the cellulose ester), an additional polymer component of the type in an amount of 5-95% by weight based on the total cellulose ester composition. Suitable examples of the additional polymer component include, but are not limited to, nylon; polyester; polyamide; polystyrene; other cellulose esters, cellulose ethers; polystyrene copolymers; styrene acrylonitrile copolymers; polyolefins; polyurethanes; acrylonitrile butadiene styrene copolymers; poly(methyl methacrylate); acrylic copolymers; poly(ether-imides); polyphenylene oxides; polyvinyl chloride; polyphenylene sulfides; polyphenylene sulfides / sulfones; poly(ester-carbonates); polycarbonates; polysulfones; polylactic acid; polybutylene succinates; polysulfone ethers; and poly(ether-ketones) of aromatic dihydroxy compounds; or mixtures of any of the above polymers. The blends can be formed by conventional processing techniques known in the art, such as melt blending or solution blending.
[0112] In one embodiment of the present invention, the composition may include a plasticizer. The plasticizer used in may be any known in the art that can reduce the glass transition temperature and / or melt viscosity of the cellulose ester to improve melt processing properties. The plasticizer may be any suitable plasticizer for use with cellulose ester. The level of plasticizer should be lower than the standard (or normal) plasticizer level for cellulose ester; the composition has a higher Tg (or HDT), better toughness, and better flowability than a fully plasticized cellulose ester composition. In some embodiments, the plasticizer is present in an amount that does not substantially reduce the Tg (or HDT) of the cellulose ester composition compared to a similar composition without the plasticizer. In some embodiments, the Tg (or HDT) does not change (e.g., decrease) by more than 20%, or more than 15%, or more than 10%, or more than 5%, or more than 2% as a result of including the plasticizer.
[0113]
[0113] The plasticizer may be of either monomeric or polymeric structure. In the method, the plasticizer is at least one selected from the group consisting of an aromatic phosphate ester plasticizer, an alkyl phosphate ester plasticizer, a dialkyl ether diester plasticizer, a tricarboxylate ester plasticizer, a polymeric polyester plasticizer, a polyglycol diester plasticizer, a polyester resin plasticizer, an aromatic diester plasticizer, an aromatic triester plasticizer, an aliphatic diester plasticizer, a carbonate plasticizer, an epoxidized ester plasticizer, an epoxidized oil plasticizer, a benzoate plasticizer, a polyol benzoate plasticizer, an adipate plasticizer, a phthalate plasticizer, a glycolate ester plasticizer, a citrate ester plasticizer, a hydroxyl functional plasticizer, or a solid amorphous resin plasticizer.
[0114] In one embodiment of the invention, the plasticizer is: triphenyl phosphate , tricresyl phosphate, cresyl diphenyl phosphate, octyl diphenyl phosphate, diphenyl biphenyl phosphate, trioctyl phosphate, tributyl phosphate, diethyl phthalate, dimethoxyethyl phthalate, dimethyl phthalate, dioctyl phthalate, dibutyl phthalate, di-2-ethylhexyl phthalate, butyl benzyl phthalate, dibenzyl phthalate, butyl phthalyl butyl glycolate, ethyl phthalyl ethyl glycolate, methyl phthalyl ethyl glycolate, triethyl citrate, tri-n-butyl citrate, acetyl triethyl citrate, acetyl-tri-n-butyl citrate, and acetyl-tri-n-(2-ethylhexyl) citrate, diethylene glycol dibenzoate, dipropylene glycol dibenzoate, or triethylene glycol dibenzoate.
[0115] In another embodiment of the invention, the plasticizer is selected from the group consisting of: (i) phthalic acid, adipic acid, and (ii) an ester comprising one or more residues of an aliphatic, alicyclic, or aromatic alcohol containing up to about 20 carbon atoms.
[0116] In another embodiment of the invention, the plasticizer is selected from the group consisting of: (i) phthalic acid, adipic acid, and (ii) at least one acid residue selected from the group consisting of an aliphatic, alicyclic, or aromatic alcohol containing up to about 20 carbon atoms.
[0117] In another embodiment of the present invention, the plasticizer may contain an alcohol residue, The alcohol residue is at least one selected from the following: stearyl alcohol, lauryl alcohol, phenol, benzyl alcohol, hydroquinone, catechol, resorcinol, ethylene glycol, neopentyl glycol, 1,4-cyclohexanedimethanol, and diethylene glycol.
[0118] In another embodiment of the invention, the plasticizer is one of the following: benzoate, phthalate, In another embodiment, the plasticizer comprises diethylene glycol dibenzoate (abbreviated herein as "DEGDB").
[0119] In another embodiment of the present invention, the plasticizer is one of the following: 10 Diacid residues, For example, residues of malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, and sebacic acid; and C2-C 10 Aliphatic polyester containing diol residues The player may select from at least one of the following:
[0120] In another embodiment, the plasticizer is selected from the group consisting of C2 to C 10 Diol: Ethylene glycol The diol residue may be at least one residue of ethylene glycol, diethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, neopentyl glycol, 1,5-pentanediol, 1,6-hexanediol, 1,5-pentylene glycol, triethylene glycol, and tetraethylene glycol.
[0121] In another embodiment of the present invention, the plasticizer may be, for example, polyethylene glycol. Examples of suitable polyglycols include polyglycols such as polypropylene glycol, polybutylene glycol, and polybutylene glycol. These may range from low molecular weight dimers and trimers to high molecular weight oligomers and polymers. In one aspect, the molecular weight of the polyglycols may range from about 200 to about 2000.
[0122]
[0122] In another aspect of the invention, the plasticizer comprises at least one of the following: Resoflex® R296 plasticizer, Resoflex® 804 plasticizer, SHP (sorbitol hexapropionate), XPP (xylitol pentapropionate), XPA (xylitol pentaacetate), GPP (glucose pentaacetate), GPA (glucose pentapropionate), and APP (arabitol pentapropionate).
[0123]
[0123] In another embodiment of the present invention, the plasticizer is (A) about 5 to about 95% by weight of C2- C 12 (B) a carbohydrate organic ester (the carbohydrate contains from about 1 to about 3 monosaccharide units); and (B) from about 5 to about 95% by weight of a C2-C 12 Polyol esters, wherein the polyol is derived from a C5 or C6 carbohydrate. In one embodiment, the polyol esters are free or do not contain one or more polyol acetates.
[0124] In another embodiment, the plasticizer comprises at least one carbohydrate ester; The carbohydrate portion of the carbohydrate ester is derived from one or more compounds selected from the group consisting of glucose, galactose, mannose, xylose, arabinose, lactose, fructose, sorbose, sucrose, cellobiose, cellotriose, and raffinose.
[0125] In another embodiment of the present invention, the plasticizer is at least one carbohydrate ester. wherein the carbohydrate portion of the carbohydrate ester comprises one or more of α-glucose pentaacetate, β-glucose pentaacetate, α-glucose pentapropionate, β-glucose pentapropionate, α-glucose pentabutyrate, and β-glucose pentabutyrate.
[0126] In another embodiment, the plasticizer comprises at least one carbohydrate ester; The carbohydrate portion of the carbohydrate ester may include an α-anomer, a β-anomer, or a mixture thereof.
[0127] In another embodiment, the plasticizer is: propylene glycol dibenzoate. In one embodiment, the benzoate may be selected from at least one of glyceryl tribenzoate, glyceryl tribenzoate, diethylene glycol dibenzoate, triethylene glycol dibenzoate, dipropylene glycol dibenzoate, and polyethylene glycol dibenzoate.
[0128]
[0128] In another embodiment of the present invention, the plasticizer may be a solid amorphous resin. These resins may contain some aromatic or polar functional groups and are the basis of cellulose esters. The melt viscosity can be reduced. In one embodiment of the present invention, the plasticizer may be a solid, non-crystalline compound (resin) such as, for example, rosin; hydrogenated rosin; stabilized rosin and their monofunctional alcohol or polyol esters; modified rosin such as, but not limited to, maleic and phenolic modified rosin and their esters; terpene resins; phenolic modified terpene resins; coumarin-indene resins; phenolic resins; alkylphenol-acetylene resins; and phenol-formaldehyde resins.
[0129] In another embodiment of the present invention, the plasticizer is triacetin, trimethylphosphene phosphate, triethyl phosphate, tributyl phosphate, triphenyl phosphate, triethyl citrate, acetyl trimethyl citrate, acetyl triethyl citrate, acetyl tributyl citrate, tributyl-o-acetyl citrate, dibutyl phthalate, diaryl phthalate, diethyl phthalate, dimethyl phthalate, di-2-methoxyethyl phthalate, dioctyl phthalate, dioctyl adipate, dibutyl tartrate, ethyl o-benzoyl benzoate, ethyl phthalyl ethyl glycolate, methyl phthalyl ethyl glycolate, n-ethyl toluenesulfonamide, o-cresyl p-tolylate benzene sulfonate, aromatic diol, substituted aromatic diol, aromatic ether, tripropionin, tribenzoin, polycaprolactone, glycerin, glycerin ester, diacetin, glycerol acetate benzoate, polyethylene glycol, polyethylene glycol ester, polyethylene glycol diester, di-2-ethylhexyl polyethylene glycol ester, triethylene glycol bis-2-ethylhexanoate, glycerol ester, diethylene glycol, polypropylene glycol, polyglycol diglycidyl ether, dimethyl sulfoxide, N-methylpyrrolidinone, C1-C 20Dicarboxylate esters, dimethyl adipate, dibutyl maleate, dioctyl maleate, resorcinol monoacetate, catechol, catechol esters, phenols, epoxidized soybean oil, castor oil, linseed oil, epoxidized linseed oil, other vegetable oils, other seed oils, polyethylene glycol based bifunctional glycidyl ethers, gamma valerolactone, alkyl phosphate esters, aryl phosphate esters, phospholipids, eugenol, cinnamyl alcohol, camphor, methoxyhydroxyacetophenone, vanillin, ethyl vanillin, 2-phenoxyethanol, glycol ethers, glycol esters, glycol ester ethers, polyglycol ethers, polyglycol esters, ethylene glycol ethers, propylene glycol ethers, ethylene glycol esters, propylene glycol and at least one plasticizer selected from the group consisting of butyl esters, polypropylene glycol esters, acetylsalicylic acid, acetaminophen, naproxen, imidazole, triethanolamine, benzoic acid, benzyl benzoate, salicylic acid, 4-hydroxybenzoic acid, propyl-4-hydroxybenzoate, methyl-4-hydroxybenzoate, ethyl-4-hydroxybenzoate, benzyl-4-hydroxybenzoate, diethylene glycol dibenzoate, dipropylene glycol dibenzoate, triethylene glycol dibenzoate, butylated hydroxytoluene, butylated hydroxyanisole, sorbitol, xylitol, ethylenediamine, piperidine, piperazine, hexamethylenediamine, triazine, triazole, pyrrole, and any combination thereof.
[0130] The amount of plasticizer in the cellulose ester composition is determined by the amount of the plasticizer in the cellulose ester composition. The amount may range from 0 to about 15 wt % based on the weight of the cellulose ester composition. In one embodiment, the amount may range up to about 15 wt % based on the weight of the cellulose ester composition. In another embodiment, the amount may range up to about 10 wt % based on the weight of the cellulose ester composition. In other embodiments, the amount may range up to about 5 wt % based on the weight of the cellulose ester composition, or up to about 3 wt % based on the weight of the cellulose ester composition, or less than 2 wt % based on the weight of the cellulose ester composition. It may be an area.
[0131] In another embodiment of the invention, the composition does not contain a plasticizer. In one embodiment, the cellulose ester composition includes a cellulose ester that is CAP and does not include a plasticizer. In one embodiment, the cellulose ester composition includes a cellulose ester that is CAB and does not include a plasticizer.
[0132] In another embodiment of the present invention, the composition is melt processable. Melt processability is achieved by: Generally, it refers to the ability of materials to be thermally processed below their decomposition temperature to obtain uniform pellets or plastic articles. For example, the compositions described are manufactured by Werner & Pflerderer It can be melt extruded at a throughput of 35 lbs / hr using a screw speed of 250 rpm and a barrel temperature of 240°C in a 30 mm twin screw extruder and injection molded with minimal molecular weight or discoloration using a barrel temperature of 240°C and a mold temperature of 160°F in a Toyo 110 injection molding machine.
[0133]
[0133] In one embodiment of the present invention, 1 to 30% by weight, or 1 to 15% by weight, or 2 A melt-processable cellulose ester composition is provided that contains ~10 wt% impact modifier and no plasticizer, has a heat distortion temperature (HDT) value greater than 95°C (measured according to ASTM-D648 at a stress level of 1.82 MPa after conditioning at 70°C for 4 hours), and a notched Izod impact strength value greater than 80 J / m (measured according to ASTM-D256 at 23°C on 3.2 mm thick bars), and a spiral flow value of at least 15 inches at 240°C measured using the procedures described herein. In one embodiment, the cellulose ester composition has a Tg value greater than 120°C measured according to ASTM-D3418 at 20°C / min.
[0134] In another embodiment of the present invention, the composition is prepared according to ASTM-D4440. Rheometrics were measured using frequency scans between 1 rad / s and 400 rad / s. The melt rheometer was designed to measure 10,000 MPa using a plate-plate melt rheometer such as a Dynamic Analysis Instrument (RDA II) with parallel plates of 25 mm diameter, a 1 mm gap, and a strain of 10%. It has a melt viscosity at 240°C and 400 rad / sec or less.
[0135]
[0135] In one embodiment, the melt-processible cellulose ester composition has a molecular weight of 0 to 30. % or 0-15 wt. % of an impact modifier, 0-15 wt. % of a plasticizer, and has a Tg greater than 90° C. In another embodiment, the melt-processable cellulose ester composition comprises 0-30 wt. % or 0-15 wt. % of an impact modifier, 0-10 wt. % of a plasticizer, and has a Tg greater than 100° C. In yet another embodiment, the melt-processable cellulose ester composition comprises 0-10 wt. % of an impact modifier, 0-10 wt. % of a plasticizer, and has a Tg greater than 100° C. In another embodiment, the melt-processable cellulose ester composition comprises 0-10 wt. % of an impact modifier, 0-5 wt. % of a plasticizer, and has a Tg greater than 115° C.
[0136] In another embodiment of the present invention, the cellulose ester composition comprises an impact modifier. The incorporation of a plasticizer results in a Tg or heat distortion temperature (HDT at 0.455 psi) that is comparable to that of the base cellulose ester polymer, with only a few degrees Celsius (e.g., less than 5°C, or less than 2°C) drop due to the lack of plasticizer incorporation. The impact properties of these compositions can also exceed 80 J / m (notched Izod impact strength at 23°C).
[0137] In some embodiments of the present invention, the polymer base resin is a cellulose ester resin having a viscosity of 1000:1 or 1000:1. 48, has a heat distortion temperature (HDT) of greater than 90°C or greater than 95°C measured at 1.82 MPa using 3.2 mm thick bars subjected to 70°C for 4 hours. In some embodiments, the polymer-based resin has a heat distortion temperature (HDT) of at least 95° C., at least 100° C., at least 105° C., or at least 110° C., or at least 115° C. In some embodiments, the polymer-based resin has a heat distortion temperature (HDT) of 90° C. to 140° C., 90° C. to 130° C., 90° C. to 120° C., 90° C. to 110° C., 95° C. to 140° C., 95° C. to 130° C., 95° C. to 120° C., 95° C. to 110° C., 95° C. to 105° C., 100° C. to 140° C., 100° C. to 130° C., 100° C. to 120° C., 100° C. to 110° C., 105° C. to 14 ...40° C., 100° C. to 140° C., 100° C. to 140° C., It has a heat distortion temperature (HDT) in the range of 5℃ to 130℃, 105℃ to 120℃, 105℃ to 115℃, 105℃ to 110℃, 110℃ to 140℃, 110℃ to 130℃, 110℃ to 125℃, 110℃ to 120℃, 110℃ to 115℃, 115℃ to 140℃, 115℃ to 130℃, 120℃ to 140℃, 120℃ to 130℃, or 120℃ to 125℃.
[0138] In some embodiments of the present invention, the polymer base resin is a cellulose ester resin having a viscosity of 1000:1 or higher, preferably 1000:1 or higher, more preferably 1000:1 or higher. 56, measured on 3.2 mm thick bars subjected to 50% relative humidity at 23° C. for 48 hours, of at least 80 J / m, or at least 90 J / m, or at least 100 J / m, or at least 110 J / m, or at least 120 J / m, or at least 130 J / m, or at least 140 J / m, or at least 150 J / m, or at least 160 J / m, or at least 170 J / m, or at least 180 J / m, or at least 190 J / m, or at least 200 J / m. In some embodiments, the polymer-based resin has a modulus of elasticity of about 80 J / m to about 500 J / m, about 80 J / m to about 400 J / m, about 80 J / m to about 300 J / m, about 80 J / m to about 200 J / m, about 100 J / m, or about 200 J / m, as measured according to ASTM-D256 using 3.2 mm thick bars subjected to 48 hours at 23° C. and 50% relative humidity. m ~ about 500J / m, about 100J / m - about 400J / m, about 100J / m - about 300J / m, about 100J / m - about 200J / m, about 120J / m - about 500J / m, Approx. 120J / m~Approx. 400J / m, Approx. 120J / m~Approx. 300J / m, Approx. 120J / m~Approx. 200J / m, Approx. 150J / m~Approx. 500J / m, Approx. 150J / m~Approx. 40 0J / m, about 150J / m to about 300J / m, about 150J / m to about 200J / m, about 170J / m to about 500J / m, about 170J / m to about 400J / m, about 170J / m ~ approx. 300J / m, approx. 170J / m ~ approx. 200J / m, 180J / m ~ approx. 500J / m, approx. 180J / m ~ approx. 400J / m, approx. 180J / m ~ approx. 300J / m, approx. It has a notched Izod impact strength in the range of 180 J / m to about 200 J / m, 190 J / m to about 500 J / m, about 190 J / m to about 400 J / m, about 190 J / m to about 300 J / m, about 190 J / m to about 200 J / m, 200 J / m to about 500 J / m, about 200 J / m to about 400 J / m, or about 200 J / m to about 300 J / m.
[0139] In another embodiment of the present invention, the cellulose ester composition further comprises an antioxidant, a heat The composition may further comprise at least one additive selected from the group consisting of stabilizers, release agents, antistatic agents, brighteners, colorants, flow aids, processing aids, plasticizers, anti-fog additives, inorganics, UV stabilizers, lubricants, chain extenders, nucleating agents, reinforcing fillers, wood or wood flour fillers, glass fibers, carbon fibers, flame retardants, dyes, pigments, colorants, additional resins, and combinations thereof.
[0140] In some embodiments, the impact modifier, cellulose ester, and optionally The mixing of the impact modifier, plasticizer, and optional additives can be carried out by any method known in the art that is suitable for dispersing the impact modifier, plasticizer, and additives in cellulose ester. Examples of mixing equipment include, but are not limited to, Banbury mixer, Brabender mixer, roll mill, and extruder (single screw or twin screw). The shear energy during mixing is determined by the combination of equipment, blade design, rotation speed (rpm), and mixing time. The shear energy must be sufficient to disperse the impact modifier throughout the cellulose ester.
[0141] In some embodiments, the cellulose ester, the impact modifier, the plasticizer, and The additives and additives can be mixed in any order during the process. In one embodiment, the cellulose ester is premixed with the impact modifier and / or plasticizer. The cellulose ester containing the impact modifier and / or plasticizer is then mixed with the additives. In another embodiment of the present invention, when a reactive impact modifier is used, the reactive impact modifier can be mixed with the cellulose ester first, and then other ingredients are added.
[0142] In some embodiments of the present invention, the cellulose ester composition comprises a cellulose ester. The ester composition comprises 2% to 15% by weight of an impact modifier based on the total weight of the ester composition, and has an HDT value of greater than 95°C, a notched Izod impact strength value of greater than 80 J / m, and a viscosity of greater than 10,000 P at 240°C and 400 rad / sec.
[0143] In another embodiment, the acetonitrile has a total DS / AGU in the range of about 2 to about 2.99. The cellulose ester composition has a DS / AGU in the range of about 0 to about 2.2, and the remainder of the ester groups include propionyl, butyryl, or a combination thereof.
[0144] In another embodiment, the melt-processable cellulose ester composition described above is In some embodiments, the plasticizer is present in an amount that does not substantially reduce the HDT of the cellulose ester composition compared to a similar composition without the plasticizer. In some embodiments, the HDT does not change (e.g., decrease) by more than 10%, or more than 5%, or more than 2% as a result of the inclusion of the plasticizer.
[0145] In one aspect, the present invention provides a polymer-based resin derived from cellulose. 1. An injection molded article comprising a thin-walled body portion formed from a fat, the thin-walled body portion comprising: (i) Gate location; (ii) final filling position; (iii) a flow length to wall thickness ratio (wherein the flow length is measured from the gate location to the final fill location) of 100 or greater; and (iv) a wall thickness of about 2 mm or less; having; The polymer-based resin has an HDT of at least 90° C., or at least 95° C., a bio-derived content of at least 20% by weight, or at least 40% by weight, and a spiral flow length of at least 3.0 cm when the polymer-based resin is molded in a spiral flow mold with a barrel temperature of 238° C., a melt temperature of 246° C., a molding pressure of 13.8 MPa, a mold thickness of 0.8 mm, and a mold width of 12.7 mm. In some embodiments, the polymer-based resin has a spiral flow length of at least 4.0 cm, or at least 5.0 cm.
[0146] In one embodiment of the injection molded article, the polymer base resin further comprises an ASTM- A flexural modulus of greater than 1900 MPa as measured using 3.2 mm thick bars at 23° C. and 50% relative humidity for 48 hours in accordance with ASTM-D790; a notched Izod impact strength of greater than 80 J / m as measured using 3.2 mm thick bars at 23° C. and 50% relative humidity for 48 hours in accordance with ASTM-D256; a flexural creep deflection of less than 12 mm as measured using molded bars having dimensions of 5 inches long, 0.5 inches wide, and 0.125 inches thick placed horizontally at 90° C. for 68 hours on a fixture with a 4 inch span and an apparent stress of 500 psi at the center of the span inside a drying oven; a permeability of at least 70 as measured using 3.2 mm plaques after injection molding at a barrel set point of 249° C. and a 5 minute residence time in accordance with ASTM-D1003; or a ΔE value of at least 85 as measured using a 3.2 mm plaque after injection molding in accordance with ASTM-E1348 at a barrel temperature of 249° C. and a 5 minute residence time. *color value. In some embodiments, the polymer-based resin has at least two, or at least three of the listed characteristics. In some embodiments, the polymer-based resin contains less than 5% by weight, or less than 4% by weight, or less than 3% by weight, or less than 2% by weight, or less than 1% by weight of plasticizer, or no added plasticizer.
[0147]
[0147] "Thickness" means the average thickness of a thin-walled body part, unless otherwise specified. In one embodiment, the wall thickness may be the average wall thickness throughout the molded article. In one embodiment, the wall thickness is substantially constant.
[0148]
[0148] "Gate location" refers to the location where the polymer to be injection molded is introduced into the mold during the injection molding process. Various types of gates can be used to produce the molded article, such as, for example, a side gate, a spoke gate, a pin gate, a submarine gate, a film gate, a disc gate, or any combination thereof.
[0149] "Final filling position" means the position at which the polymer is intended to be filled during injection molding. It is the location in the mold cavity that is furthest from the port location.
[0150] "Gate size" is the diameter of the gate opening if it is a circular gate. For non-circular gate openings, this is the effective diameter, or the smallest dimension of the opening.
[0150]
[0151] In some embodiments, the gate location includes a gate having a gate dimension. The ratio of gate size to wall thickness is 1:1 or less, or 0.9:1 or less, or 0.8:1 or less, or 0.7:1 or less, or 0.6:1 or less, or 0.5:1 or less. In some embodiments, the gate location includes a gate having a gate size, and the ratio of gate size to wall thickness is in the range of 1:1 to 0.1:1, or 0.9:1 to 0.1:1, or 0.8:1 to 0.1:1, or 0.7:1 to 0.1:1, or 0.6:1 to 0.1:1, or 0.5:1 to 0.1:1.
[0151]
[0152] In some embodiments, the gate size is 1.0 mm or less, or 0.9 mm or less. In some embodiments, the wall thickness is 1.9 mm or less, or 1.8 mm or less, 1.7 mm or less, or 1.6 mm or less, 1.5 mm or less, or 1.4 mm or less, or 1.3 mm or less, 1.2 mm or less, or 1.1 mm or less, 1.0 mm or less, or 0.9 mm or less, 0.8 mm or less, or 0.7 mm or less, 0.6 mm or less, or 0.5 mm or less.
[0152]
[0153] In some embodiments, the ratio of flow length to wall thickness is at least 100, or is at least 150, or at least 200, or at least 250, or at least 300, or at least 350, or at least 400, or at least 450, or at least 500, where the flow length is measured from the gate position to the final filling position. In some embodiments, the ratio of the flow length to the wall thickness is 100 to 1500, or 100 to 1250, or 100 to 1000, or 100 to 750, or 150 to 1500, or 150 to 1250, or 150 to 1000, or 150 to 750, or 200 to 1500, or 200 to 1250, or 200 to 1000, or 200 to 750, or 250 to 1500, or 200 to 1250, or 200 to 1000, or 250 to 750, or 300 to 1500, or 300 to 1250, or 300 to 1000, or 300 to 750, or 350 to 1500, or 350 to 1250, or 350 to 1000, or 350 to 750. , or 400-1500, or 400-1250, or 400-1000, or 400-750, or 450-1500, or 450-1250, or 450-1000, or 450-750, or 500-1500, or 500-1250, or 500-1000, or 500-750, where the flow length is measured from the gate position to the final fill position.
[0153]
[0154] In some embodiments of the present invention, the molded article has a diameter of less than about 1.0 millimeter. for wall thicknesses less than about 0.75 millimeters; a ratio of flow length to wall thickness greater than about 350, such as a ratio of about 350 to about 1250; for wall thicknesses less than about 0.5 millimeters; a ratio of greater than about 200, such as a ratio of about 300 to about 1000, for wall thicknesses less than about 1 millimeter; a ratio of greater than about 200, such as a ratio of about 200 to about 1000, for wall thicknesses less than about 0.375 millimeters; a ratio of greater than about 200, such as a ratio of about 250 to about 750, for wall thicknesses less than about 0.375 millimeters; and a ratio of greater than about 150, such as a ratio of about 150 to about 500, for wall thicknesses less than about 0.25 millimeters.
[0154]
[0155] In some embodiments, the polymer-based resin forming the injection molded article comprises: The resin is selected from any of the cellulose ester compositions discussed herein. In one embodiment, the resin is a cellulose ester composition comprising a CAP, a secondary antioxidant, and an acid scavenger, and has an HDT greater than 95° C. In one embodiment, the cellulose ester composition further comprises 1-30 wt % of an impact modifier, less than 2 wt % of a plasticizer (or no plasticizer), and less than 5 wt %, or less than 2 wt % of any other additives.
[0155]
[0156] The present invention can be further illustrated by the following examples of preferred embodiments thereof, It will be understood that these examples are included for illustrative purposes only and are not intended to limit the scope of the invention unless otherwise specifically stated. EXAMPLES
[0156]
[0157] The present invention can be further illustrated by the following examples of its embodiments. The examples are included for illustrative purposes only and are not intended to limit the scope of the invention unless otherwise specifically stated.
[0157]
[0158] Abbreviation:
[0159] Ex is an example; CA is cellulose acetate; CAB is cellulose %H is haze; %T is transmittance; M is cellulose acetate butyrate; CAP is cellulose acetate propionate; %H is haze; %T is transmittance; M is w is the absolute weight average molecular weight, and ΔM w % is percent change in absolute weight average molecular weight; %H is percent haze; RH is relative humidity; °C is degrees Celsius; min is minutes; °F is degrees Fahrenheit; Comp. Ex. is comparative example; Pz is plasticizer; Antiox is antioxidant; SNMO is AKCROSTAB AN-MO; Temp is temperature; min is minutes; NPPP is WESTON Neo is pentyl phenyl phosphite; Prim is primary; IM is impact modifier; Scav is scavenger; Stab is stabilizer; CE is cellulose ester; oz is ounces; in / sec is inches per second; sec or s is seconds; psi is pounds per square inch; BSP is barrel set point; RT is residence time.
[0158]
[0160] The basic steps for preparing the composition are:
[0161] These examples are based on the use of cellulose ester powders as stabilizers, impact modifiers, and The mixture was prepared by premixing the mixture with additives such as cellulose acetate and plasticizers in a Hobart mixer for 20 minutes at room temperature.
[0159]
[0162] Example 1:
[0163] Example 1 contains Eastman® CAP 482-20 (18.484 lbs, 92.42 wt%), ECO 100 (1.2 lbs, 6.0 wt%), IRGANOX 1010 (0.05 lbs, 1.0 wt%), and 0.25 wt.%, IRGAFOS 168 (0.066 lbs., 0.33 wt.%), DRAPEX 4.4 (0.194 lbs., 0.97 wt.%), SNMO (0.0006 lbs., 0.03 wt.%) % by volume was prepared by mixing in a Hobart mixer for 20 minutes at room temperature.
[0160]
[0164] To determine the effect of different stabilizers on the important properties shown in the examples in Table 1, A series of compositions were prepared to demonstrate the effectiveness of the acrylic resins used in these examples. The compound was CAP482-20 (registered trademark).
[0161]
[0165]
[0162] [Table 1]
[0163]
[0166] Comparative Example 1 is a conventional plasticized CE compound made from CAP482-20, which has low Comparative Example 1 is a comparative example for low HDT. Comparative Example 2 was prepared by adapting the procedure disclosed above and is a comparative example for some embodiments of the present invention where low ΔE and / or high transmission is required. The base material used for these comparative examples was Eastman® )CAP482-20.
[0164]
[0167]
[0165] [Table 2]
[0166]
[0168] Pellet production:
[0169] The premixed materials (Examples 1-13 and Comparative Examples 1-4) were then fed into the throat of a Davis-Standard 32 mm extruder and mixed at a screw speed of 300 rpm and a barrel temperature of 225° C. at a throughput of 40 lbs / hr for the Eastman® CAP482-20 based composition to produce pellets.
[0167]
[0170] Plaque preparation:
[0171] Pellets of the mixed material were then heated at 249°C (480°F) or 250°C (100°F) in a 150-ton Toyo injection molding machine with a 6.7 oz barrel capacity and an injection speed of 1 in / sec. Two 4 inch x 4 inch x 0.126 (10.2 cm x 10.2 cm x 0.32 cm) plaques were injection molded per shot using a nominal barrel temperature of 60°C (500°F), a residence time of 2 or 5 minutes, and a mold temperature of 80°C.
[0168]
[0172] Preparation of test bars:
[0173] Pellets of the mixed material were injection molded into 0.5" x 5" x 0.1" Standard test bars measuring 25 inches (1.27 cm x 12.7 cm x 0.3 cm) were formed. The pellets were molded in a 110 ton Toyo injection molding machine with a barrel capacity of 3.4 ounces. Typically, the mixed material is injection molded into four test bars per shot at an injection rate of 1 inch / second using a nominal barrel temperature of 249°C (480°F) and a mold temperature of 80°C.
[0169]
[0174] Test Method:
[0175] The samples were subjected to standard ASTM test methods and one of the special conditions listed below. It was used to evaluate.
[0170]
[0176]
[0171] [Table 3]
[0172]
[0177] Spiral Flow:
[0178] 3.2mm thick bar stock:
[0179] A reciprocating screw with a screw diameter of 32 mm and a clamping force of 110 tons A 300 mm long injection molding machine was fitted with a water cooled cold runner mold having a helical shaped cavity with dimensions 0.50 inch wide x 0.125 inch deep x 60.00 inch long. The cavity was fed through a 3.5 inch long cold sprue with a 0.400 inch nominal diameter and a 3° taper, then a 1.0 inch long cold runner with a 0.30 inch nominal diameter, then a rectangular gate measuring 0.25 inch wide x 0.050 inch thick x 0.10 inch long. Variables controlled for the scope of the experiment included resin drying, injection unit barrel temperature, mold temperature, initial injection rate, injection pressure limit, screw rotation speed, and back pressure for screw recovery, injection time, and cycle time.
[0173]
[0180] For each variable combination, the response includes the actual melt temperature, and the helical shape. The melt travel distance within the mold cavity (excluding runners and gates) was included. The injection process was allowed to stabilize at each set of conditions (usually 10-15 shots) and then 10 molded specimens were collected with the average flow length reported.
[0174]
[0181] All materials were cast at an initial rate of 1 in / sec with pressure control and a mold temperature of 80°F. The molded parts were molded using an injection speed of 1000 psi, an injection unit pressure limit of 10 seconds, a cycle time of 38 seconds, a maximum cushion of 0.1 inches, a screw recovery rotation speed of 150 rpm, and a screw recovery back pressure of 100 psi.
[0175]
[0182] 0.8mm thick bar stock:
[0183] A reciprocating screw with a screw diameter of 32 mm and a clamping force of 110 tons The injection molding machine was fitted with a water-cooled cold runner mold having a spiral shaped cavity with dimensions of 0.50 inches wide by 0.030 inches deep by 60.00 inches long. The cavity contained a 3.5 inch long tube with a 0.400 inch nominal diameter and a 3° taper. The injection mold was fed through a 2.0 inch cold sprue, then a 1.0 inch long cold runner with a 0.30 inch apparent diameter, then a rectangular gate measuring 0.25 inch wide by 0.030 inch thick by 0.10 inch long. Variables controlled for the range of experiments included resin drying, injection unit barrel temperature, mold temperature, initial injection rate, injection pressure limits, screw rotation speed, and back pressure for screw recovery, injection time, and cycle time.
[0176]
[0184] For each variable combination, the response includes the actual melt temperature, and the helical shape. The melt travel distance within the mold cavity (excluding runners and gates) was included. The injection process was allowed to stabilize at each set of conditions (usually 10-15 shots) and then 10 molded specimens were collected with the average flow length reported.
[0177]
[0185] All materials were molded using pressure control at a mold temperature of 120°F (49°C) and a 1 inch The molded parts were molded using an initial injection rate of 100 / sec, an injection unit pressure limit of 2000 psi, a 5 second injection time, a 32 second cycle time, a maximum cushion of 0.2 inches, a screw recovery rotation speed of 150 rpm, and a screw recovery back pressure of 100 psi.
[0178]
[0186] Test results:
[0187] The results in Table 4 below (Examples 1 to 13 and Comparative Examples 2 to 4) are The injection molding conditions and the color value (L) of the obtained plaques were determined by molding the plaques into 4 inch x 4 inch plaques from pellets of the material. * , a* , b * ), %H, and %T. The M of cellulose ester after molding at the pellet stage and plaque stage is given. w %ΔM w (pellet to plaque conversion rate).
[0179]
[0188]
[0180] [Table 4-1]
[0181] [Table 4-2]
[0182]
[0189] Table 5 shows the results for Comparative Examples 1, 3, and 4, and Examples 2, 3, 12, and 13. Notched Izod, heat distortion temperature, and flexural modulus are given.
[0190]
[0183] [Table 5]
[0184]
[0191] Table 6 gives the spiral flow data for Examples 12-13 and Comparative Example 3. can.
[0192]
[0185] [Table 6]
[0186]
[0193] ESCR: Retention of characteristics in rear impact:
[0194] The tests were performed on lengths of 5.0 inches, 0.5 inches, and 0.125 inches, respectively. The bending tests were performed using injection molded bend test bars having a length of 1 mm, width, and thickness. The bars were conditioned for a minimum of 72 hours at 23°C / 50% RH. The bars were clamped in a constant strain test fixture or a three-point bend fixture at 1.5% strain and exposed to the chemical reagents using a wet patch method for low viscosity or volatile materials or direct application for high viscosity materials. The reagents were applied on the side of the bar not having the ejector pin marks and the strain test fixture with the bar attached was sealed in a polyethylene bag for 24 hours at an apparent temperature of 23°C, after which the bar was wiped clean and removed from the strain test fixture.
[0187]
[0195] The bars were then stored at 23°C for 24-96 hours after removal from the strain test fixture. The bars were tested for rear impact using a CEAST Pendulum impact tester fitted with a 15 Joule hammer. The bars were placed in a 2 inch span fixture with the side not exposed to the chemical facing the hammer. Four control bars (no distortion, no chemical exposure) were impact tested in addition to the four chemical exposed bars. Comparison of the results between the control bars and the chemical exposed bars was used to calculate the % retention of the original impact energy.
[0188]
[0196]
[0189] [Table 7]
[0190]
[0197] ESCR: Retention of properties in tensile tests:
[0198] The tests were performed on lengths of 8.5 inches, 0.5 inches, and 0.125 inches, respectively. The tests were performed using injection molded tensile test bars having a diameter of 1.0 mm, center width, and thickness. The bars were conditioned for a minimum of 72 hours at 23° C. / 50% RH. The bars were clamped in a constant strain fixture at 1.0% strain and exposed to chemical reagents using a wet patch method for low viscosity or volatile materials or direct application for high viscosity materials. After the reagents were applied onto the side of the bar not having the ejector pin marks, the strain fixture with the bar attached was sealed in a polyethylene bag for 24 hours at an apparent temperature of 23° C., after which the bar was wiped clean and removed from the strain fixture.
[0191]
[0199] The bars were then stored at 23°C for 24-96 hours after removal from the strain test fixture. The test equipment was an Instron tensile tester equipped with a 10 kN load cell. The bar was placed in the jaws with a 4.5 inch span between the jaws. The bars were placed in a tensile test position and pulled to break at 0.2 in / min for the first 0.03 in and 2.0 in / min for the remainder of the pull. In addition to the five bars exposed to the chemicals, five control bars (no strain, no chemical exposure) were tensile tested. Comparison of the results between the control bars and the chemical exposed bars was used to calculate the % retention of original break strength and break elongation.
[0192]
[0200]
[0193] [Table 8]
[0194]
[0201] Bending creep deflection:
[0202] A projectile having dimensions of 5 inches long, 0.5 inches wide, and 0.125 inches thick. The extruded bend test bars were placed horizontally inside an oven on a fixture with a 4 inch span, following the test procedure of ASTM-D2990. A weight was hung from each bar at the center of the span, and the mass was selected to impart a nominal stress of 500 psi on the bend test bars.
[0195]
[0203] The bar with the weight hanging from it is left exposed in the oven for a specified period of time. After exposure was completed, the weights were removed from the bars, the bars were allowed to cool to room temperature in ambient air, and were measured for 4 inch free span deflection.
[0196]
[0204]
[0197] [Table 9]
[0198]
[0205] Dimensional change during moisture test:
[0206] A projectile having dimensions of 5 inches long, 0.5 inches wide, and 0.125 inches thick. The extruded bend test bars were immersed in deionized water at 85° C. for 310 hours to achieve maximum water absorption. Prior to immersion, the bars were conditioned at 23° C. / 50% RH for 48 hours.
[0199]
[0207] The weight and dimensions of the bar were measured before and after immersion in water and the % change in length was calculated. The average of three test bars was recorded for each test.
[0208]
[0200] [Table 10]
[0201]
[0209] Examples 14 to 39 in Tables 11 to 15 were prepared as follows. In a drum tumbler, cellulose powder was mixed with 1% epoxidized octyl talc stabilizer. They were premixed with either KaneAce B564-MBS impact modifier from Kaneka Corporation, or KaneAce ECO100 acrylic impact modifier from Kaneka Corporation.
[0202]
[0210] The premixed material was then fed into a Werner & Pflerderer 30mm twin screw extruder. The feedstock was run at a screw speed of 250 rpm and a CAP 482 base oil at a throughput of 35 lbs / hr. The blends were mixed at a barrel temperature of 220°C for the cellulose compositions and 240°C for the CA and CAP 141-20 based compositions.
[0203]
[0211] Next, the mixed material was put into a Toyo 110-ton injection molding machine and cooled to 240°C. The mixture was injection molded into 3.2 mm thick x 12.8 mm wide bars using a cast temperature of 100°C and a mold temperature of 70°C.
[0204]
[0212] The cellulose ester materials used in the examples were selected from Eastman products CAP 482-20, CAP-482-0.5, and CAP 141-20. The samples (for Examples 14-39) were: Heat distortion temperatures (HDT) were determined on the molded bars according to ASTM method D648 as discussed above except that they were conditioned by placing in a 70° C. oven for 5 hours prior to HDT testing.
[0205]
[0213] The material compositions and properties for Examples 14-39 are shown in Tables 11-15.
[0212]
[0206] [Table 11]
[0207]
[0213]
[0208] [Table 12]
[0209]
[0214]
[0210] [Table 13]
[0211]
[0215]
[0212] [Table 14]
[0213]
[0216]
[0214] [Table 15]
[0215]
[0217] Considering Tables 11 to 15, Examples 15 to 36 and 38 to 39 have improved impact resistance. It is shown that the toughness is higher than that of Examples 14 and 37 which do not contain additives.
[0218] Melt processability of Example 26:
[0219] Using the spiral flow test, the flow behavior of Example 26 from Table 12 above was The plastic materials were compared to those of the 1990s and 2000s. Spiral flow tests were performed using a Toyo 110 ton molding machine to fill a 0.5 inch wide by 0.125 inch thick spiral flow mold with molten material using an injection pressure of 1000 psi, an injection rate of 1.0 in / sec, a fill time of 10 seconds, a screw speed of 150 rpm, 100 psi back pressure, and a cooling time of 22 seconds. The flow length is the length of the spiral of each material molded at a particular barrel temperature under the same molding conditions.
[0216]
[0220] First, spiral flow was performed to obtain the flow length values of several polymer materials. The materials used were Makrolon 2458 polycarbonate (PC) from Covestro, Lustran SAN31 (styrene-acrylonitrile or SAN) from INEOS, and Terluran GP22NR-ABS from INEOS. These materials were tested at the processing temperatures shown in Table 16 below.
[0217]
[0221] In addition to the materials discussed above, the spiral flow was used for Example 26 and Comparative Example 3. These materials were tested at the processing temperatures shown in Table 16.
[0222]
[0218] [Table 16]
[0219]
[0223] A review of Table 16 reveals that flow length values for commercial materials range from 10 to 30 inches. It can be seen that the spiral flow of Example 26 shows that this composition has very good flowability (similar to ABS and SAN, and better than PC), indicating that the inventive examples can be melt processed in injection molding and other processes. Comparative Example 3 (fully plasticized with CAP, but no impact modifier) had the highest spiral flow length.
[0220]
[0224] In Examples 40 to 44, the cellulose ester composition contains CAP 482-20, The compositions were prepared by blending with several block copolymer thermoplastic elastomers and additional impact modifiers such as ABS core-shell impact modifiers. The blending of the cellulose ester compositions was carried out in a Leistritz 18mm (50:1 L / D ratio) twin screw extruder at a throughput of 18 lbs / hr, a screw speed of 250 rpm, and a barrel temperature of 220°C. For the blending of the CA and CAP 141-20 based compositions, the barrel temperature was 230°C. The blended materials were then injection molded into 3.2mm thick x 12.8mm wide bars in a Toyo 110 ton injection molding machine using a barrel temperature of 240°C and a mold temperature of 70°C. The properties of these compositions are compared to Example 14 in Table 17.
[0221]
[0225] ASTM standard method D34, where the sample is heated from -110°C at a heating rate of 20°C / min. Glass transition temperatures (Tg) were measured according to 18. DSC scans of blends of materials may show multiple Tg transitions. If more than one Tg transition is found during a scan, the glass transition of the matrix is defined as the highest Tg measured during the scan.
[0222]
[0226] For a 3.2 mm thick molded bar, the bar was heated at 230°C and 50% RH. After conditioning for 48 hours, notched Izod impact strength testing was performed at 23° C. after notching according to ASTM method D256.
[0223] [Table 17]
[0224] Other embodiments will be apparent to those skilled in the art from consideration of the specification and practice of the embodiments disclosed herein. It is understood that changes and modifications can be made within the spirit and scope of the disclosed embodiments. Further, it is intended that the specification and examples be considered as exemplary only, with a true scope and spirit of the disclosed embodiments being indicated by the following claims.
Claims
1. 1. A molded article comprising a cellulose-derived polymer-based resin, the polymer-based resin having a HDT of at least 95° C., a bio-derived content of at least 20 wt. %, a notched Izod impact strength greater than 80 J / m as measured using 3.2 mm thick bars at 23° C. and 50% relative humidity for 48 hours according to ASTM-D256, and a flexural modulus greater than 1900 MPa as measured using 3.2 mm thick bars at 23° C. and 50% relative humidity for 48 hours according to ASTM-D790; a spiral flow length of 10.0 cm; a flexural creep deflection of less than 12 mm as measured using a molded bar having dimensions of 5 inches long, 0.5 inches wide, and 0.125 inches thick, placed horizontally inside a drying oven at 90° C. for 68 hours on a fixture with a 4 inch span and an apparent stress of 500 psi on the center of the span; a permeability of at least 70 as measured using a 3.2 mm plaque after injection molding at a barrel set point of 249° C. and a 5 minute residence time according to ASTM-D1003; a ΔE value of less than 25 using a 3.2 mm plaque after injection molding at a barrel temperature of 249° C. and a 5 minute residence time; or an L of at least 85 as measured using a 3.2 mm plaque after injection molding at a barrel temperature of 249° C. and a 5 minute residence time according to ASTM-E1348. * and color value.
2. 2. The molded article of claim 1, wherein the polymer-based resin has a HDT in the range of 95°C to 140°C.
3. The molded article of claim 2, wherein the polymer-based resin has a HDT in the range of 100°C to 140°C.
4. The molded article according to any one of claims 1 to 3, wherein the polymer-based resin has a content of bio-derived components in the range of 20% to 60% by weight.
5. The shaped article according to any one of claims 1 to 4, wherein the polymer-based resin has a content of bio-derived components in the range of 40% to 60% by weight.
6. The molded article of any of claims 1 to 5, wherein the polymeric base resin has at least two of the listed properties.
7. The shaped article of any of claims 1 to 6, wherein the polymer-based resin comprises less than 4% by weight of a plasticizer.
8. The shaped article of any of claims 1 to 7, wherein the polymer-based resin comprises a cellulose ester.
9. 9. The shaped article of claim 8, wherein the cellulose ester is selected from CA, CAP, CAB, or CAIB.
10. 10. The shaped article of claim 9, wherein the cellulose ester is CAP.
11. The shaped article of claim 10, wherein the CAP is plasticizer-free.
12. 10. The shaped article of claim 9, wherein the cellulose ester is CA.
13. The shaped article of claim 12, wherein the CA comprises a plasticizer in an amount of 1 to 10 wt %.
14. 12. The molded article of any one of claims 1 to 11, wherein the polymer-based resin is a CAP, the CAP having an HDT of at least 95°C; a bio-derived content of at least 40% by weight; a spiral flow length of at least 5.0 cm when the polymer-based resin is molded in a spiral flow mold with a barrel temperature of 238°C, a melt temperature of 246°C, a molding pressure of 13.8 MPa, a mold thickness of 0.8 mm, and a mold width of 12.7 mm; a bending creep deflection of less than 10 mm measured using a molded bar having dimensions of 5 inches long, 0.5 inches wide, and 0.125 inches thick, placed horizontally inside a drying oven at 90°C for 68 hours with an apparent stress of 500 psi on the center of the span on a fixture with a 4 inch span; and a ΔE value of less than 25 using a 3.2 mm plaque after injection molding at a barrel temperature of 249°C and a 5 minute residence time.
15. 15. The molded article of any of claims 1 to 14, wherein the molded article can be selected from an injection molded article, an extrusion molded article, a rotational molded article, a compression molded article, a blow molded article, an injection blow molded article, an injection stretch blow molded article, an extrusion blow molded article, a sheet or film extrusion article, a profile extrusion article, a gas assisted molded article, a structural foam molded article, or a thermoformed article.
16. The molded article according to any one of claims 1 to 15, wherein the molded article can be selected from transparent articles, see-through articles, thin-walled articles, industrial articles, articles with advanced design specifications, articles with intricate designs, articles produced from molds that are difficult to fill under normal molding operations or conditions, worn articles, articles that come into contact with the body, containers, articles that come into contact with food, household articles, general consumer products, packaging articles, medical articles, or parts thereof.
Citation Information
Cited By
Depiction device and adjustment method
CN122652902A